Expert Evaluation of Artificial Intelligence Chatbots for Central Auditory Processing Disorder Information - Davidson, Alyssa J.; Jedrzejczak, W Wiktor; McCullagh, Jennifer; Ferre, Jeanane M.; Bradbury, Amy; Palmer, Shannon B.; Iliadou, Vasiliki M.; Musiek, Frank E. (American journal of audiology, 2026)
PURPOSE: Artificial intelligence (AI) chatbots based on large language models (LLMs) can deliver medical information, but their performance on specialized topics such as central auditory processing disorder (CAPD) remains unexplored. This study evaluated the accuracy and completeness of three AI chatbots (ChatGPT, Gemini, and Claude) in providing CAPD-related information across varying levels of question complexity. METHOD: Forty-four questions, categorized into four difficulty levels (patient level, easy, intermediate, and specialized; n = 11 each), were submitted to each chatbot, generating 132 responses. Seven clinical experts, blinded to chatbot identity, independently rated accuracy and completeness on a 1-5 Likert scale. Data were analyzed with analyses of variance, correlations, and interrater comparisons. RESULTS: Chatbot performance was similar, with mean accuracy below 4.0 and completeness about 3.5. Complex questions often scored below 3.0 across experts. Only three of the 44 questions, primarily patient level or relatively simple, received consistently high expert ratings (≥ 4 for both accuracy and completeness) across all three chatbots. Performance declined with question difficulty, although differences were not statistically significant. Accuracy and completeness were correlated across chatbots. CONCLUSIONS: Current AI chatbots provided generally accurate CAPD information but fell short of clinical standards, particularly on specialized questions. Their limited performance underscores the need for clinician oversight in CAPD assessment and management. Chatbots may serve as helpful adjuncts but should not replace expert evaluation and guidance in clinical settings. SUPPLEMENTAL MATERIAL: https://doi.org/10.23641/asha.31975101.
Keywords: dept.cmd

Expert evaluation of artificial intelligence chatbots for central auditory processing disorder information - Davidson, Alyssa; Jedrzejczak, W.; McCullagh, Jennifer; Ferre, Jeanane; Bradbury, Amy; Palmer, Shannon; Iliadou, Vasiliki; Musiek, Frank (American Journal of Audiology, 2026)
Keywords: Chatbot; Completeness (order theory); Expert system; Inter-rater reliability; Psychometrics; Telemedicine; dept.cmd

Incorporating gender-inclusive language in undergraduate courses on anatomy and physiology of the speech mechanism - Smith, Julian; Smith, Keith; White, Evan (Perspectives of the ASHA Special Interest Groups, 2025)
Keywords: Competence (human resources); Cultural competence; Curriculum; English language; Language acquisition; Mechanism (biology); Multiculturalism; dept.cmd

Identifying the association between post-extubation laryngeal edema and aspiration in acute respiratory failure patients - DM, Lucas; R, Peterson; J, Rieck; M, Owusu; E, McNally; R, Scheel; P, Cavanagh; S, Langmore; A, Kearney; J, Levitt; J, Siner; R, Vojnik; et al. (European Archives of Oto-Rhino-Laryngology, 2026)
Keywords: Acute pulmonary edema; Acute respiratory failure; Aspiration; Deglutition disorders; Edema; Laryngeal Edema; Laryngeal edema; Larynx; Post-extubation dysphagia; Pulmonary edema; Respiratory failure; dept.cmd

Reliability of Lingual Swallow Pressure Measurements in Healthy Older and Younger Adults - Smith, Julian; Murray, Kelsey; Szynkiewicz, Sarah; Wasiuk, Peter; Dalton, M; Thompson, Kirsty; Kamarunas, Erin (Journal of Oral Rehabilitation, 2025)
Keywords: Bolus (digestion); Mastication; Measurement device; Reliability (semiconductor); Swallowing; dept.cmd; dysphagia; lingual strength; reliability; swallow pressureswallowingtongue strength

Imaging of the Velopharynx: Nasopharyngoscopy - Kummer, Ann W.; Mabry, Kelly (Cleft Palate and Velopharyngeal Dysfunction: A Multidisciplinary Approach to Evaluation and Management, 2025)
Nasopharyngoscopy is a minimally invasive endoscopic procedure that allows visual observation and analysis of the velopharyngeal mechanism during speech. It can be used to assess both anatomic and physiologic abnormalities of the velopharyngeal valve. In cases of suspected velopharyngeal insufficiency (VPI), nasopharyngoscopy is particularly useful in determining the size, location, and cause of the velopharyngeal opening. This information is very important for surgical planning. Nasopharyngoscopy is also useful in the assessment of secondary surgery that was done for VPI. It can help determine the need for revision and the type of revision surgery that is most likely to be successful. The purpose of the chapter is to explain how nasopharyngoscopy is used in the evaluation of velopharyngeal function. This chapter includes specific tips for achieving a successful examination in children as young as age 3. Finally, important observations from nasopharyngoscopy are described. © 2025 The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Hypernasality; Instrumental assessment; Medicine; Nasal emission; Nasendoscopy; Nasopharyngoscopy; Resonance disorder; Velopharyngeal dysfunction; Velopharyngeal incompetence; Velopharyngeal insufficiency; Velopharyngeal valve; dept.cmd

Masked-Speech Recognition and Self-Reported Functional Listening in Autistic Young Adults - Wasiuk, Peter; Cook, Barbara; Irwin, Julia (Journal of Speech Language and Hearing Research, 2025)
Keywords: Active listening; Audiology; Autism; Cognitive psychology; Communication; Developmental psychology; Medicine; Perception; Psychology; Speech perception; dept.cmd; dept.psy

Beginning Reading Instruction for Students at Risk for Reading Disabilities: What, How, and When - Coyne, Michael D.; Zipoli, Richard P.; Ruby, Maureen F. (Intervention in School and Clinic, 2006)
In this article, the authors assist teachers who are working with young students at risk for reading disabilities by helping make sense of the large—but unwieldy—scientific knowledge base. They offer a conceptual framework for thinking about beginning reading instruction and intervention across three dimensions: the content of instruction (what to teach), the delivery of instruction (how to teach), and the timing of instruction (when to teach). The authors discuss each of these dimensions and describe how teachers can use them to help organize and make sense of what we know about beginning reading instruction for students experiencing reading difficulties.
Keywords: dept.cmd; peer-reviewed

Enhancing Vocabulary Intervention for Kindergarten Students: Strategic Integration of Semantically Related and Embedded Word Review - Zipoli, Richard P.; Coyne, Michael D.; McCoach, D. Betsy (Remedial and Special Education, 2011)
Two approaches to systematic word review were integrated into an 18-week program of extended vocabulary instruction with kindergarten students from three high-need urban schools. Words in the embedded and semantically related review conditions received systematic and distributed review. In the embedded review condition, brief word definitions were integrated into the narratives of multiple storybooks. In the semantically related review condition, in-depth word review with explicit emphasis on semantic features and associations was provided during extension activities. Systematic review resulted in an almost twofold increase in target word learning. Embedded review was effective and time efficient, whereas semantically related review was time intensive but resulted in higher levels of word learning. There was a significant gain in Peabody Picture Vocabulary Test—III standard scores following the intervention.
Keywords: dept.cmd; peer-reviewed

Effects of a Supplemental Vocabulary Intervention on the Word Knowledge of Kindergarten Students at Risk for Language and Literacy Difficulties - Loftus, Susan M.; Coyne, Michael D.; McCoach, D. Betsy; Zipoli, Richard; Pullen, Paige C. (Learning Disabilities Research & Practice, 2010)
The purpose of this study was to examine the effectiveness of a vocabulary intervention designed to supplement research–based classroom vocabulary instruction, implemented with students who may be at risk for language and learning difficulties. Participants included 43 kindergarten students who received research–based classroom vocabulary instruction. Students with the 20 lowest scores on the Peabody Picture Vocabulary Test–III administered at pretest received additional small–group supplemental vocabulary intervention. Results of within–subjects comparisons indicated that, overall, at–risk students made greater gains in word knowledge on target words that received the supplemental intervention as compared to words that received only classroom–based instruction. In addition, at–risk students who received the supplemental intervention demonstrated word–learning gains that approached those of their peers who received classroom instruction alone. Implications along with limitations of the current study and directions for future research are discussed.
Keywords: dept.cmd; peer-reviewed

Effective Strategies for Teaching Reading Comprehension. - Coyne, M. D.; Chard, D. J.; Zipoli, R. P.; Ruby, M. F. (Effective Teaching Strategies that Accommodate Diverse Learners, 2010)
Keywords: dept.cmd

Fiberoptic Endoscopic Evaluation of Swallowing (FEES) with and without Blue-Dyed Food - Leder, Steven B.; Acton, Lynn M.; Lisitano, Heather L.; Murray, Joseph T. (Dysphagia, 2005)
The purpose of this prospective study was to determine if fiberoptic endoscopic evaluation of swallowing (FEES) maintains high intra- and interrater reliability in detecting pharyngeal dysphagia and aspiration without the addition of FD&C Blue No. 1 to food. Twenty consecutive adults referred for a swallow evaluation participated. Nine subjects received blue-dyed food and 11 subjects received regular nondyed food, i.e., yellow pudding and white skim milk. Four variables were rated: (1) the stage transition characterized by depth of bolus flow to at least the vallecula prior to the pharyngeal swallow; (2) evidence of bolus retention in the vallecula or pyriform sinuses after the pharyngeal swallow; (3) laryngeal penetration defined as material in the laryngeal vestibule but not passing below the level of the true vocal folds either before or after the pharyngeal swallow; and (4) tracheal aspiration defined as material below the level of the true vocal folds either before or after the pharyngeal swallow. Three speech–language pathologists experienced in interpreting FEES results independently and blindly reviewed the digitized videotape three times. Intrarater agreements for the four variables with blue-dyed and non-blue-dyed food trials were 100% and monochrome trials ranged from 95% to 100%. Average kappa values for interrater reliability ranged from moderate to excellent agreement (0.61–1.00) for all viewing conditions. Kappa values for blue-dyed trials versus monochrome trials were 0.83 and for non-blue-dyed trials versus monochrome trials were 0.88, indicative of excellent reliability under both viewing conditions. FEES maintains both high intra- and interrater reliability in detecting the critical features of pharyngeal dysphagia and aspiration using either blue-dyed or non-blue-dyed foods. The endoscopist, therefore, can be assured of reliable FEES results using regular, non-dyed food trials.
Keywords: Aspiration; Blue dye; Deglutition; Deglutition disorders; Fiberoptic endoscopic evaluation of swallowing; Pharyngeal dysphagia; dept.cmd; peer-reviewed

Answering Orientation Questions and Following Single-Step Verbal Commands: Effect on Aspiration Status - Leder, Steven B.; Suiter, Debra M.; Lisitano Warner, Heather (Dysphagia, 2009)
In the acute-care setting patients with altered mental status as a result of such diverse etiologies as stroke, traumatic brain injury, degenerative neurologic impairments, dementia, or alcohol/drug abuse are routinely referred for dysphagia testing. A protocol for dysphagia testing was developed that began with verbal stimuli to determine patient orientation status and ability to follow single-step verbal commands. Although unknown, it would be beneficial to ascertain if this information on mental status was predictive of aspiration risk. The purpose of this investigation was to determine if there was a difference in odds for aspiration based upon correctly answering specific orientation questions, i.e., 1. What is your name? 2. Where are you right now? and 3. What year is it?, and following specific single-step verbal commands, i.e., 1. Open your mouth. 2. Stick out your tongue. and 3. Smile. In a consecutive retrospective manner data from 4070 referred patients accrued between 1 December 1999 and 1 January 2007 were analyzed. The odds of liquid aspiration were 31% greater for patients not oriented to person, place, and time (odds ratio [OR] = 1.305, 95% CI = 1.134–1.501). The odds of liquid aspiration (OR = 1.566, 95% CI = 1.307–1.876), puree aspiration (OR = 1.484, 95% CI = 1.202–1.831), and being deemed unsafe for any oral intake (OR = 1.688, 95% CI = 1.387–2.054) were, respectively, 57, 48, and 69% greater for patients unable to follow single-step verbal commands. Being able to answer orientation questions and follow single-step verbal commands provides information on odds of aspiration for liquid and puree food consistencies as well as overall eating status prior todysphagia testing. Knowledge of potential increased odds of aspiration allows for individualization of dysphagia testing thereby optimizing swallowing success.
Keywords: Aspiration; Cognition; Deglutition; Deglutition disorders; peer-reviewed

Initiating Safe Oral Feeding in Critically Ill Intensive Care and Step-Down Unit Patients Based on Passing a 3-Ounce (90 Milliliters) Water Swallow Challenge - Leder, Steven B.; Suiter, Debra M.; Warner, Heather L.; Kaplan, Lewis J. (Journal of Trauma and Acute Care Surgery, 2011)
Background: Pulmonary aspiration is a leading cause of nosocomial infection in the intensive care unit (ICU) and step-down unit (SDU). A key goal is to identify patients who exhibit increased aspiration risk before beginning oral alimentation. This study investigated the success of recommending specific oral diets to ICU and SDU patients based on passing a 3-oz water swallow challenge. Methods: A referral-based sample of 401 ICU and 92 SDU patients were prospectively analyzed. Amount of liquid and food ingested at the next day's meal 12 hours to 24 hours after passing a 3-oz challenge and specific diet recommendations were accessed electronically from oral intake information entered on each participant's daily care sheets. Drinking and eating success, clinically evident aspiration events, and accuracy of diet order recommendations were recorded. Care providers were blinded to the purpose of the study. Results: All 401 ICU and 92 SDU patients were successfully drinking thin liquids and eating 12 hours to 24 hours after passing a 3-oz challenge. Mean volume of liquid ingested at the next day's meal was 360 mL ± 181.2 mL for ICU and 356.4 mL ± 173.5 mL for SDU patients. Percent of meal eaten ranged from 10% to 100%. Patient care sheets indicated specific diet recommendations were followed with 100% accuracy. Conclusions: Successfully recommending specific oral diets for ICU and SDU patients based on passing a 3-oz water swallow challenge was supported. Importantly, when a simple bedside 3-oz challenge administered by a trained provider is passed, specific diet recommendations can be made safely and confidently without the need for further objective dysphagia testing.
Keywords: dept.cmd; peer-reviewed

Effect of Presence/Absence of a Nasogastric Tube in the Same Person on Incidence of Aspiration - Fattal, Michael; Suiter, Debra M.; Warner, Heather L.; Leder, Steven B. (Otolaryngology–Head and Neck Surgery, 2011)
Objective. To determine what effect, if any, the presence or absence of a nasogastric (NG) tube in the same person had on the incidence of anterograde aspiration. Design. Case series with planned data collection. Setting. Large, urban, tertiary care teaching hospital. Subjects and Methods. Referred sample of 62 consecutively enrolled adult inpatients for fiber-optic endoscopic evaluation of swallowing (FEES). Group 1 (n = 21) had either small-bore (n = 13) or large-bore (n = 8) NG tubes already in place and had a FEES first with the NG tube in place and a second FEES after NG tube removal. Group 2 (n = 41) did not have an NG tube and had a FEES first without an NG tube and a second FEES after placement of a small-bore NG tube. Time between FEES was approximately 5 minutes. Patients were tested with thin liquid and puree food consistencies. Occurrence of aspiration for each consistency dependent on the presence or absence of an NG tube was recorded. Results. There were no significant differences (P > .05) in aspiration status for both liquid and puree consistencies in the same person dependent on presence or absence of either a small-bore or large-bore NG tube. Conclusions. Since objective swallowing evaluation (eg, FEES) can be performed with an NG tube in place, it is not necessary to remove an NG tube to evaluate for aspiration. Similarly, there is no contraindication to leaving an NG tube in place to supplement oral alimentation until nutritional requirements are achieved.
Keywords: dept.cmd; peer-reviewed

Deaf-Blind - McCullagh, Jennifer; Weiss, Deborah (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Screening Test for Auditory Processing Disorders - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Pediatric Speech Intelligibility Test - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Otitis Media - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Hearing - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Dichotic Listening - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Deafness - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Cochlea - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Brainstem Audiometry - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Auditory Brainstem Response, ABR - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Comparisons of P300s from Standard Oddball and Omitted Paradigms: Implications to Exogenous/Endogenous Contributions - McCullag, Jennifer; Weihing, Jeffrey; Musiek, Frank (Journal of the American Academy of Audiology, 2009)
Purpose: To compare the amplitude, latency, morphology, and threshold of the auditory P300 using standard oddball and omitted paradigms. Research Design: P300 waveforms were measured from the Cz electrode site. Frequent stimuli for both paradigms were 1000 Hz tone bursts. Target stimuli for the standard oddball paradigm were 2000 Hz tone bursts and an omitted stimulus, or silent gap, for the omitted paradigm. Study Sample: Fifteen bilaterally normal-hearing young adults. Results: There were significantly lower amplitudes, poorer morphology, and higher thresholds for the P300 using an omitted paradigm compared to the standard oddball paradigm. Conclusion: These results suggest that the auditory P300 could have a larger exogenous component than traditionally thought.
Keywords: Key Words Endogenous; P300; dept.cmd; exogenous; intensity effects; omitted paradigm; peer-reviewed

Oral Reading Assessment: Four Conditions Where Caution Is Warranted - Zipoli, R.P.; Ramachandar, S. (Assessment for Effective Intervention, 2023)
Assessments of oral reading are widely used for screening, progress monitoring, and comprehensive evaluations. Despite the utility and technical adequacy of these tools, there are subgroups of students for whom measures of oral reading may be inappropriate. The first section of this article focuses on how tests of oral reading may underestimate word reading ability and reading fluency among four subgroups of students with speech, language, or learning difficulties. These include school-age students who demonstrate word-finding difficulties (which are common among students with a learning disability or developmental language disorder), developmental stuttering, childhood apraxia of speech, and pediatric dysarthria. The second section offers practical recommendations for more accurate assessment procedures, correct placement decisions, relevant professional learning activities, and strategic interdisciplinary teaming. © Hammill Institute on Disabilities 2023.
Keywords: communication disorders; dept.cmd; learning disability; peer-reviewed; reading/literacy

Speaking and Reading in Two Languages: On the Identification of Reading and Language Disabilities in Spanish-Speaking English Learners - Francis, David J.; Rojas, Raúl; Gusewski, Svenja; Santi, Kristi L.; Khalaf, Shiva; Hiebert, Lindsey; Bunta, Ferenc (New Directions for Child and Adolescent Development, 2019)
Articles in this issue examine (1) the primary sources of variability in reading and language achievement among Spanish-speaking English learners (ELs) in the United States, (2) the extent to which poor performance at the end of grade 2 is identifiable in developmental trajectories beginning in kindergarten, (3) the relations among core reading constructs of phonological awareness and decoding in both English and Spanish and the factors that affect their relationship, (4) the performance of different approaches to identification and the factors that influence how well they work, as well as (5) the growing literature focused on intervention for reading problems in this population. This article examines the literature on language minority students and disability identification and analyzes a large-scale longitudinal dataset (>4,000 ELs; >15,000 observations) to systematically characterize and describe the oral language and reading development of Spanish-speaking children designated as ELs from kindergarten to second grade, considering a range of factors that may potentially contribute to that characterization and its relation to academic performance. This systematic characterization should facilitate the development of an empirical basis for a theoretically grounded framework of typical development in ELs in order to more precisely identify those children with language and learning disabilities.
Keywords: dept.cmd; peer-reviewed

Moving Forward by Looking Back: Understanding Why Some Spanish-Speaking English Learners Fall Behind - Rojas, Raúl; Hiebert, Lindsey; Gusewski, Svenja; Francis, David J. (New Directions for Child and Adolescent Development, 2019)
This study investigated early indicators of Spanish-speaking English learners (ELs) at risk for reading difficulties at the end of Grade 2 by examining their early bilingual oral language development, taking into account language of academic instruction. Standardized measures of reading and narrative samples were collected in English and Spanish from kindergarten to Grade 2 from 1,243 ELs primarily instructed in English or Spanish. Conditional growth curve models yielded four primary findings of reading and oral language development. First, ELs with low reading achievement at the end of Grade 2 demonstrated early reading difficulties during kindergarten. Second, although ELs demonstrated overall higher reading achievement in their instructed language, this difference decreased over time. Third, ELs with low reading achievement at the end of Grade 2 demonstrated lower oral language skills in each language over time. Fourth, ELs demonstrated overall higher oral language skills in their instructed language, yet these differences varied over time. The study provided a detailed description of the longitudinal relations among the bilingual reading and oral language skills of Spanish-speaking ELs during the early school years. These findings help to inform the processes of early identification and intervention for Spanish-speaking ELs who are likely to demonstrate reading achievement difficulties.
Keywords: dept.cmd; peer-reviewed

Predicting speech-in-speech recognition: Short-term audibility and spatial separation - Wasiuk, P.A.; Calandruccio, L.; Oleson, J.J.; Buss, E. (Journal of the Acoustical Society of America, 2023)
Quantifying the factors that predict variability in speech-in-speech recognition represents a fundamental challenge in auditory science. Stimulus factors associated with energetic and informational masking (IM) modulate variability in speech-in-speech recognition, but energetic effects can be difficult to estimate in spectro-temporally dynamic speech maskers. The current experiment characterized the effects of short-term audibility and differences in target and masker location (or perceived location) on the horizontal plane for sentence recognition in two-talker speech. Thirty young adults with normal hearing (NH) participated. Speech reception thresholds and keyword recognition at a fixed signal-to-noise ratio (SNR) were measured in each spatial condition. Short-term audibility for each keyword was quantified using a glimpsing model. Results revealed that speech-in-speech recognition depended on the proportion of audible glimpses available in the target + masker keyword stimulus in each spatial condition, even across stimuli presented at a fixed global SNR. Short-term audibility requirements were greater for colocated than spatially separated speech-in-speech recognition, and keyword recognition improved more rapidly as a function of increases in target audibility with spatial separation. Results indicate that spatial cues enhance glimpsing efficiency in competing speech for young adults with NH and provide a quantitative framework for estimating IM for speech-in-speech recognition in different spatial configurations. © 2023 Acoustical Society of America.
Keywords: dept.cmd; peer-reviewed

Aphasia, alexia, and agraphia - Purdy, Mary H. (Encyclopedia of Mental Health, Third Edition: Volume 1-3, 2023)
Aphasia is a language disorder that occurs as a result of brain damage. It affects auditory comprehension, verbal expression, reading, and writing due to the disruption of specific language components such as phonology, semantics, and/or syntax. A hallmark characteristic of aphasia is anomia, or impaired word retrieval. This may occur in the context of fluent speech (normal rate, rhythm and prosody) or nonfluent speech (hesitant and agrammatic verbal output). Other characteristics of aphasia vary depending on the specific location and extent of brain damage. Alexia and agraphia are acquired impairments in reading and writing, respectively. These deficits may occur in isolation but more commonly co-occur with aphasia. Assessment and treatment of aphasia, alexia, and agraphia focuses on identifying and restoring impaired function as well as determining the impact of the impairment of quality of life and developing compensatory strategies to manage persisting deficits. This article describes the symptoms associated with aphasia, alexia, and agraphia, the subtypes and neurological correlates of each impairment, the general trajectory of recovery, and assessment and treatment approaches. © 2023 Elsevier Inc. All rights reserved.
Keywords: Acquired language disorders; Agraphia; Alexia; Aphasia; Communication disorder; Dysgraphia; Dyslexia; Dysphasia; dept.cmd

Utilization of instrumentation in swallowing assessment of surgical patients during COVID-19 - Warner, Heather; Coutinho, Jennifer M.; Young, Nwanmegha (Life, 2023)
The aim of this study is to describe a measured return to instrumental dysphagia assessments for our vulnerable surgical patient population, such that best practice patterns could be resumed and our staff kept safe from transmission of COVID-19. A retrospective medical record review provided data on clinical practice patterns of swallowing assessment in an at-risk surgical patient population. Outcomes of this study support protocols that allow clinicians to safely resume the use of instrumental assessment and return to best practice in dysphagia assessment for our surgical patient population.
Keywords: COVID-19; Fiberoptic Endoscopic evaluation of swallowing; deglutition; dept.cmd; dysphagia; peer-reviewed; surgical; swallowing assessment

Interdisciplinary Management of Stroke Clients. - Purdy, Mary H. (2006)
Keywords: dept.cmd; faculty_collection; sabbatical_report

Communication Disorders and Persons with Developmental Disabilities. - Cascella, Paul W. (2002)
Keywords: dept.cmd; faculty_collection; sabbatical_report

Assessment of Code-Based Reading Skills by Speech-Language Pathologists. - Zipoli, Richard P. (2018)
The purpose of the sabbatical leave was to (a) review the extensive body of research and clinical literature on code-based reading difficulties and (b) prepare a journal manuscript and conference presentation to disseminate clinical information to a wide audience of school-based speech-language pathologists.
Keywords: dept.cmd; faculty_collection; sabbatical_report

A cross-sectional investigation of disfluencies in typically developing Spanish-English bilingual children - Rojas, Raúl; Irani, Farzan; Gusewski, Svenja; Camacho, Natalia (Journal of Fluency Disorders, 2023)
Purpose This study examined the language skills and the type and frequency of disfluencies in the spoken narrative production of typically developing Spanish-English bilingual children. Method A cross-sectional sample of 106 bilingual children (50 boys; 56 girls) enrolled in kindergarten through Grade 4, produced a total of 212 narrative retell language samples in English and Spanish. A specialized fluency coding system was implemented to index the percentage of total (%TD) and stuttering-like disfluencies (%SLD) in each language. Large-scale reference databases were used to classify children’s dual language proficiency profiles (balanced, English dominant, Spanish dominant) based on language sample analysis measures of morphosyntax and lexical diversity. Results The bilingual Spanish-English children in this study did not demonstrate significant cross-linguistic differences for mean %TD or %SLD. However, the mean %TD and %SLD in both languages exceeded the risk threshold based on monolingual English-speaking norms. English dominant bilingual children demonstrated significantly lower %TD in English than Spanish. Spanish dominant children demonstrated significantly lower %SLD in Spanish than English. Conclusions This study included the largest sample size of bilingual Spanish-English children investigated to date from a fluency perspective. The frequency of disfluencies was found to be variable across participants and change dynamically as a function of grade and dual language proficiency profiles, indicating the need for studies that employ larger sample sizes and longitudinal designs.
Keywords: Bilingual children; Disfluencies; Language sample analysis; Narratives; Stuttering; dept.cmd; peer-reviewed

The influence of side-lying position on oropharyngeal swallow function in at-risk infants: an exploratory study - Smith, Julian B.; Kamarunas, Erin; O’Donoghue, Cynthia (Clinical Pediatrics, 2023)
This investigation assessed the effect of side-lying position on infant oropharyngeal swallow physiology. Infant modified barium swallow studies (MBS) recordings were retrospectively examined in matched-pairs comparing at-risk infants swallowing in both an upright/cradled position and a side-lying position. Swallow parameters were measured independently and through a consensus coding approach. Infants fed in side-lying position showed a decrease in airway invasion severity as compared with when those same infants were fed in an upright/cradled position (P = .009). Bolus location at the time of swallow initiation was higher when infants were fed in side-lying position as compared with cradle position (P = .024), representing decreased risk of airway invasion. Infants fed in side-lying position demonstrated fewer swallows per breaths (P = .032). This pilot study validates the need for additional research to further define the mechanisms related to this improvement, and to determine how diagnosis and medical stability moderate these findings.
Keywords: dept.cmd; peer-reviewed

Interdisciplinary considerations for diagnosing aphasia in the schizoaffective patient: A case report - Warner, Heather; Cometz, Alexa (International Journal of Language & Communication Disorders, 2023)
Background Patients with schizophrenia present with both cognitive impairment as well as language difficulties. There are similarities in the language output of patients with schizophrenia and patients with aphasia, thus a differential diagnosis of patients who present with a question of dual diagnoses can be a clinical challenge. This case report highlights the importance of an interdisciplinary approach to a patient with schizophrenia who benefitted from intervention from both psychiatry and speech–language pathology services due to the patient's unique verbal output. Aims The primary aim of this case report is to highlight the critical importance of interdisciplinary collaboration in this patient population. The secondary aim is to disseminate an interesting and unique clinical phenomenon whereby the patient demonstrated an awareness of two distinct speech patterns and the unique ability to ‘code switch’ between them, something not commonly appreciated in this clinical population. Methods & Procedures This case report describes a patient seen as part of routine clinical care. Information shared was solely observational and involved dissemination of information regarding case history, assessment and treatment plan. No interventions were implemented as a part of this study. Outcomes & Results Interprofessional communication was critical in order to diagnose a patient with schizophrenia with an atypical speech pattern. The patient's language output did not manifest as a true aphasia but rather as two distinct language patterns that the patient could use at will. This ability to ‘code switch’ between languages is a unique clinical profile that is atypical of patients with schizophrenia. WHAT THIS PAPER ADDS What is already known on this subject Contemporary literature discusses the similarities between the language patterns of patients with aphasia and those with schizophrenia. There has been debate about how to classify and identify the mechanism of schizophrenic language. It is unclear whether the tangential press of speech in schizophrenia is a consequence of a formal thought disorder, or whether it constitutes an actual disorder or expressive language. Additionally, the mechanism for this speech pattern is not well defined in the literature as there is no consensus on whether it is a breakdown in linguistic processing or simply a patient's disordered thoughts being put into words. A less robust literature exists that suggests that there is a cognitive mechanism responsible for these speech patterns, as tangential speech has been linked to poor goal maintenance in other types of cognitive tasks. What this paper adds to existing knowledge This study adds an important discussion about the critical importance of interprofessional collaboration when differentially diagnosing this complex patient population. It highlights the importance of the clinical exchange of information between the two disciplines of psychiatry and speech–language pathology about a patient population where clinical information is intertwined in the way described above. Regardless of the cause of the disordered output, what is lacking in the literature is evidence of how to address the complexities of the output of these patients and how to best manage the care of the patient. This study adds a practical clinical approach to collaborating on the assessment and management of this complex patient population. Importantly, it adds a description of a clinical manifestation of the language output of a patient with schizophrenia that we do not believe to have been previously published in the literature. What are the potential or actual clinical implications of this work? Implications of this study include a much-needed shift in the field in two regards. First, to include this patient population in the groups of patients that can benefit from interprofessional collaboration for differential diagnosis and consideration for speech and language therapy. Second, it offers a practical clinical approach to inter-professional management in this patient population, something the literature is currently lacking. Additionally, publication of this unique clinical manifestation provides foundational knowledge for other clinicians appreciating similar clinical patterns of language output. To our knowledge, this is the first published case in which a patient could volitionally inhibit certain speech characteristics and thus this case study may assist in future differential diagnosis of patients with schizophrenia.
Keywords: aphasia; dept.cmd; interprofessional practice; language disorders; peer-reviewed; schizoaffective disorder

Effects of Teacher-Delivered eCoaching on Paraeducators and Students with Autism Spectrum Disorder - Horn, A.L.; Rock, M.L.; Douglas, K.H.; Bean, K.M.; Layden, S.J.; Roitsch, J. (Education and Training in Autism and Developmental Disabilities, 2022)
Paraeducators often support students with the most intensive academic, life, and behavioral needs, which includes students with intellectual and other developmental disabilities (IDD; e.g., autism spectrum disorder; ASD), yet they typically enter the classroom with inadequate preparation to perform their roles effectively. Using a multiple-baseline research design replicated across participants, we evaluated the effects of job-embedded bug-in-ear (BIE) coaching delivered by the teacher on paraeducators’ use of behavior specific praise (BSP) while teaching transition-age students with ASD. Findings confirmed each of the three paraeducators immediately increased the percentage of occurrence and rate per minute in which they offered BSP. They sustained these high levels during fading. Further, the special education teacher, who served as the eCoach, and the paraeducators reported BIE was an effective form of paraeducator professional development. Finally, changes in expressive social and communicative behaviors were observed in student participants as a result of the intervention. These results extend literature on BSP and also help establish BIE coaching as an evidence-based practice for paraeducators. © Division on Autism and Developmental Disabilities.
Keywords: dept.cmd; peer-reviewed; ⛔ No DOI found

Making Sense of Word Reading Difficulties: Principles of Clinical Assessment - Zipoli, Richard P. (Communication Disorders Quarterly, 2022)
Speech-language pathologists (SLPs) are increasingly called upon to help assess students with word-recognition difficulties, including dyslexia. Although SLPs tend to have comparatively strong knowledge regarding the phonological awareness skills that support word reading, findings from survey research indicate that many SLPs report limited knowledge and training on word recognition and phonics. The purpose of this article is to provide a systematic framework for assessing and interpreting students’ word reading skills. Five potential components of word reading assessment will be examined: word recognition, phonological decoding, automaticity, performance with specific phonics patterns, and reading multimorphemic and multisyllabic words. Emphasis will be given to how specific test formats and procedures can be used to help identify patterns of word reading difficulty.
Keywords: assessment; automaticity; decoding; dept.cmd; peer-reviewed; phonics; reading; word recognition

Best Practice in Swallowing Assessment in COVID-19 - Warner, Heather; Young, Nwanmegha (Dysphagia, 2022)
The COVID-19 pandemic has significantly altered the world as we know it. Service delivery for the instrumental evaluation of dysphagia in hospitalized patients has been significantly impacted. In many institutions, instrumental assessment was halted or eliminated from the clinical workflow, leaving clinicians without evidence-based gold standards to definitively evaluate swallowing function. The aim of this study was to describe the outcomes of an early, but measured return to the use of instrumental dysphagia assessment in hospitalized patients during the COVID-19 pandemic. Data was extracted via a retrospective medical record review on all patients on whom a swallowing consult was placed. Information on patient demographics, type of swallowing evaluation, and patient COVID status was recorded and analyzed. Statistics on staff COVID status were also obtained. Over the study period, a total of 4482 FEES evaluations and 758 MBS evaluations were completed. During this time, no staff members tested COVID-positive due to workplace exposure. Results strongly support the fact that a measured return to instrumental assessment of swallowing is an appropriate and reasonable clinical shift during the COVID-19 pandemic.
Keywords: COVID; Deglutition; Dysphagia; FEES; Swallowing assessment; dept.cmd; peer-reviewed

Physical Activity, Sports Participation, and Psychosocial Health in Adolescents With Hearing Loss - DeLuca, Zara Waldman; Rupp, Kristie (Journal of Adolescent Health, 2022)
Purpose This study examined the association between hearing status (i.e., adolescents with and without hearing loss) and physical activity and sports participation. Secondarily, we explored the association between physical activity and sports participation and psychosocial outcomes among adolescents with hearing loss. Methods Analyses included 29,034 adolescents (52.1% male, 13.8 ± 2.3 (M ± SD) years) from the combined 2018–2019 National Survey of Children's Health. Adolescents were grouped by hearing status. Adjusted logistic regression models assessed physical activity level (i.e., 0, 1–3, 4–6, and 7 days/week) and sports participation (i.e., participation in sports within the past 12 months) by hearing status. Secondary analyses examined associations between physical activity and sports participation with psychosocial outcomes among adolescents with hearing loss adjusting for relevant confounders. Results Relative to their hearing peers, adolescents with hearing loss (n = 359) were 40% [adjusted odds ratio (AOR), 0.60; 95% confidence interval (CI), 0.44, 0.81], 43% [AOR, 0.57; 95% CI, 0.41, 0.80], and 33% [AOR, 0.67; 95% CI, 0.47, 0.95] less likely to engage in 1–3 days/week of physical activity, 4–6 days/week of physical activity, and meet physical activity guidelines, respectively. Further, adolescents with hearing loss were 31% [AOR, 0.69; 95% CI, 0.55, 0.85] less likely to participate in sports. Sports participation, but not physical activity, was associated with a significant reduction in the likelihood of experiencing adverse psychosocial outcomes among adolescents with hearing loss (p's < .05). Discussion Sports participation, but not physical activity, was associated with attenuated likelihood of experiencing adverse psychosocial outcomes in adolescents with hearing loss, suggesting unique characteristics of sports participation confer protection of psychosocial health. Increasing access to and reducing barriers to engagement in sports should be prioritized to improve psychosocial health in adolescents with hearing loss.
Keywords: Hearing loss; Physical activity; Psychosocial health; Sports participation; dept.cmd; dept.hms; peer-reviewed

Teaching Children with Autism to Create Multi-symbol Messages on Augmentative Alternative Communication Applications During Play - Gevarter, Cindy; Najar, Adriana Medina; Siciliano, Mariah (Advances in Neurodevelopmental Disorders, 2022)
Research involving the use of augmentative and alternative communication (AAC) applications on mobile technology devices for children with autism spectrum disorder (ASD) needs to expand beyond teaching simple requesting skills. Children’s abilities to create multi-symbol AAC messages is one skill that can be further explored.
Keywords: Augmentative alternative communication; Autism; Multi-symbol messages; Naturalistic intervention; dept.cmd; peer-reviewed

Clinical efficacy of electrophysiologic measures in APD management programs - Jirsa, R.E. (Seminars in Hearing, 2002)
Determining the relative efficacy of various intervention programs for auditory processing disorders (APD) is a major goal in the field of rehabilitative audiology. Currently, because of their widespread availability, the most commonly used measuring tools to assess the central auditory system have been behaviorally based. Such measures do have notable disadvantages in that they may be influenced by a number of extraneous variables that may impede, or at least influence, efficacy measures. Electrophysiologic measures offer unique advantages not available from the behavioral measures. A significant amount of research has been completed offering compelling evidence relative to the clinical utility of a number of these electrophysiologic measures, including the maximum length sequences-auditory brainstem response, the middle latency response, the obligatory long latency responses, and the MMN and P3 event-related potentials. This article will review the current research related to electrophyiologic measures and present a rationale for including them in the management program.
Keywords: Clinical efficacy; Electrophysiology; Middle latency response; Mismatch negativity; P3 event-related potential; Speech perception; auditory nervous system; clinical practice; dept.cmd; diagnostic accuracy; diagnostic procedure; electrophysiology; event related potential; evoked auditory response; human; middle latency response; mismatch negativity; perception deafness; review; speech perception

Executive function ability in persons with aphasia - Purdy, M. (Aphasiology, 2002)
Background: There is an increasing recognition that the communication problems one observes in persons with aphasia extend beyond verbal deficits and that the myriad of symptoms observed are not solely due to a faulty linguistic system. Rather, there exists a coalition of causal elements resulting in a wide range of communicative deficits. There is some preliminary evidence suggesting that communicative success of clients with aphasia may depend on the integrity of executive function skills. Executive functions are called into play when an individual is involved in a complex, novel activity. They allow us to plan, sequence, organise, and monitor goal-directed activities in a flexible manner as demanded by situational and environmental changes. When linguistic skills are impaired, individuals need to rely on other cognitive skills in order to communicate. Aims: The purpose of this study was to explore executive functioning ability in persons with aphasia. Methods & procedures: A total of 15 individuals with aphasia and 12 healthy control subjects participated in this study. Three dimensions of performance were examined (accuracy, speed, and efficiency) in the context of neuropsychological tests designed to examine cognitive flexibility and goal-directed planning (Wisconsin Card Sorting Test, Porteus Maze Test, Tower of London, and Tower of Hanoi). Outcomes & results: Results indicated that the two groups performed with similar levels of accuracy on two of the four tests. However, significant differences were found on all speed and efficiency variables, suggesting decreased executive functioning skills in the group of individuals with aphasia. Conclusions: It is important to consider executive functioning ability in clients with aphasia and attempt to determine the influence of executive function skill on communicative performance. Understanding the cognitive abilities as well as the linguistic abilities of these clients may ultimately help clinicians determine which patients are better candidates for intervention as well as which treatment approaches would be most efficient and beneficial.
Keywords: Wisconsin card sorting test; accuracy; adult; aged; aphasia; article; clinical article; cognition; communication disorder; comparative study; controlled study; dept.cmd; human; interpersonal communication; language ability; linguistics; maze test; mental function; mental performance; neuropsychological test; peer-reviewed; planning; skill; treatment planning

Script knowledge following stroke - Purdy, M.H. (Journal of Medical Speech-Language Pathology, 2002)
This study examined script knowledge in 20 subjects who sustained a stroke (10 with left hemisphere brain damage and aphasia and 10 with right hemisphere brain damage) and 10 neurologically normal subjects. Script knowledge was examined via performance on three tasks: procedural sequencing, procedure production, and procedural discourse. Neurologically normal subjects performed all tasks accurately, and all subjects in the stroke group completed at least one of the three tasks for each script accurately, suggesting that script knowledge was preserved in this mildly brain-damaged population. However, significant differences were obtained between the neurologically normal and stroke groups when overall performance was examined. These findings suggest that additional cognitive processes influence task performance. Implications of these findings are discussed.
Keywords: adult; aged; aphasia; article; clinical article; controlled study; dept.cmd; female; human; information processing; language ability; left hemisphere; male; priority journal; right hemisphere; stroke; task performance; ⛔ No DOI found

Communication and its development in autism spectrum disorders - Paul, R. (Autism and Pervasive Developmental Disorders, Second Edition, 2007)
Introduction Communication deficits are one of the core symptoms of autism spectrum disorders (ASDs). People with ASD can be slow to begin talking, or may not learn to talk at all; others may learn to produce words and sentences but have difficulty using them effectively to accomplish social interactive goals. In this chapter we will discuss the course of the development of communication in ASD and will outline how communication deficiencies in this population are identified and treated. Before we do, however, we should be clear about three important terms we will be using, which are illustrated in Figure 4.1. The term “communication” is the broadest of this trio. It refers to all forms of sending and receiving messages, not only with language, but in other ways, such as with gestures, body language, even the way we dress. Animals can also communicate by means of their vocalizations to alert others to danger, for example. That's why the largest circle in Figure 4.1 represents communication. Within the realm of communication, language represents a specific type, so it is enclosed within the larger circle of communication in the figure. Language involves the creation of a potentially infinite set of never-before-conveyed messages through the combination of words in rule-governed ways that allow the formation of sentences to express meaning to others. © Cambridge University Press, 2007 and 2009.
Keywords: dept.cmd

Multimodal communication training in aphasia: A pilot study - Purdy, M.; Van Dyke, J.A. (Journal of Medical Speech-Language Pathology, 2011)
Management of patients with aphasia often focuses on training nonverbal augmentative communication strategies; however, these strategies frequently do not generalize to natural situations. The limited success may be because training was not sufficient to produce an integrated multimodal semantic representation. The purpose of this study was to examine whether simultaneous training of stimuli in both verbal and nonverbal modalities would solidify the links within the semantic network and improve switching among modalities as needed in conversation. Two individuals with severe aphasia participated in 6 to 8 hours of Multimodal Communication Training (MCT), during which they conveyed a concept by verbalizing, gesturing, writing, and drawing. After practice with all modalities for a single concept, a new concept was introduced. Results showed that one participant increased conveyance of concepts on the functional communication task using a variety of modalities. Although some improvement was seen with the second participant, his overall performance remained poor, likely because of a greater impairment in semantic knowledge. After a brief period of semantic training, the second participant demonstrated additional gains. Thus, MCT may serve to increase switching among verbal and nonverbal modalities in individuals with intact semantic representations, thereby increasing the likelihood that individuals will use an alternative method to communicate. Copyright © 2011 Delmar Cengage Learning.
Keywords: AAC; Aphasia; Cognition; Multimodality; Treatment; adult; aged; article; ataxic aphasia; case report; communication skill; concept formation; cortical sensory aphasia; dept.cmd; disease severity; drawing; gesture; human; male; multimodal communication training; priority journal; semantic memory; task performance; verbalization; writing; ⛔ No DOI found

Comparison of reading performance in fluent and non-fluent aphasia - Purely, M.; Newman, D. (2011)
Keywords: dept.cmd

Parsing pragmatics - Rivers, K.O.; Hyter, Y.D.; DeJarnette, G. (ASHA Leader, 2012)
Keywords: dept.cmd

Foreword - Paul, R. (Single-Word Reading: Behavioral and Biological Perspectives, 2007)
Keywords: dept.cmd

More than words - Wallace, S.; Purdy, M. (ASHA Leader, 2013)
Keywords: dept.cmd

An uncommon case: Cleft palate, respiratory compromise, and klippel-feil anomaly - Langevin, K.M.; Mabry, K.; Castiglione, C. (Plastic Surgical Nursing, 2014)
Keywords: Cervical Vertebrae; Cleft Palate; Female; Humans; Infant, Newborn; Klippel-Feil Syndrome; Spinal Fusion; cervical vertebra; cleft palate; complication; dept.cmd; female; genetics; human; newborn; procedures; spine fusion

A parent-implemented embedded AAC intervention for teaching navigational requests and other communicative functions to children with Autism spectrum disorder. - Gevarter, Cindy; Groll, Mariah; Stone, Erin; Najar, Adriana Medina (Augmentative and alternative communication (Baltimore, Md. : 1985), 2021)
This study evaluated the effectiveness of an embedded naturalistic intervention for teaching augmentative and alternative communication (AAC) application responses to three preschool-aged males with autism spectrum disorder (ASD). Parents were taught to embed opportunities for their child to communicate with a grid-based AAC application during every-day routines such as play or mealtime. Communication targets included requesting objects using two-step taxonomic navigational responses, and requesting assistance, rejecting items, or making social comments/responses using a two-step message-strip response. During intervention, parents used strategies such as time delay, prompting, reinforcement, and device proximity (faded over time) to encourage target responses. Display formats and intervention targets were selected in consideration of prior dynamic assessment results. Effects of intervention were evaluated using a multiple probe across participants design. For functional navigational AAC item requesting, all three participants showed an immediate increase in responding that maintained at high levels. Functional AAC responding for other communicative purposes also increased, but at a more gradual pace. All three participants showed generalized responding when new items were added to displays, and when display pages with a larger array of folders and vocabulary items were introduced. Generalization to labeling tasks was mixed. © 2021 International Society for Augmentative and Alternative Communication.
Keywords: Alternative communication; Augmentative and alternative communication application; Augmentative-and-alternative communication; Autism spectrum disorders; Communication application; Communicative functions; Diseases; Embedded instruction; Human rehabilitation engineering; Naturalistic intervention; Navigation; Steps responding; Two-step responding; dept.cmd; peer-reviewed

Naturalistic communication training for early intervention providers and latinx parents of children with signs of autism. - Gevarter, Cindy; Najar, Adriana Medina; Flake, Jennifer; Tapia-Alvidrez, Felicia; Lucero, Alixandria (Journal of developmental and physical disabilities, 2021)
In this study, researchers implemented a brief training plus coaching program in naturalistic developmental behavioral intervention with three participant triads. Each triad consisted of an early intervention provider, an English-speaking Latinx parent, and that parent’s young child with autism spectrum disorder (ASD) or early signs of ASD who had limited vocal speech. The effects a single training session, plus two researcher coaching sessions were evaluated using a nonconcurrent multiple probes across participants design. Primary dependent variables included (a) the number of completed targeted communication turns between the parent and child and (b) the number of child independent target communication responses (gestures and manual signs) during family-selected routines. Additional measures examined whether parents used strategies taught to them during training, and whether early intervention providers addressed strategies taught via coaching. A social validity measure was used to determine parent and provider views of the training. Due to COVID-19 restrictions, training and post-training sessions were delivered via telehealth for two triads. While data trends and variability differed across triads, following training, all three families increased the number of completed target communication turns and all three children showed higher rates of independent communication responses. Parents and providers implemented strategies taught and reported positive effects of the program. Implications regarding the use of naturalistic intervention methods for Latinx families, the utility of brief training models to meet the needs of under-resourced early intervention programs, and potential uses of telehealth are discussed. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: dept.cmd; peer-reviewed

Maximum length sequences-auditory brainstem responses from children with auditory processing disorders - Jirsa, R.E. (Journal of the American Academy of Audiology, 2001)
This study was designed to evaluate maximum length sequences-auditory brainstem responses (MLS-ABR) in children with auditory processing disorders and to compare these results with a normal control group matched for age, intelligence, and gender. Although each waveform was analyzed for the presence of waves I, III, and V, the primary focus was wave V. Although absolute latency measures for wave V were obtained from all subjects, waves I and III were not always identified. Although the results showed latency increases for all waveforms in both groups, the only significant difference noted was an increase in wave V latency for both the left and right ears in the clinical group. These results suggest that the MLS-ABR may be useful in the assessment of auditory processing disorders. Implications for the potential use of the MLS-ABR in management programs are discussed.
Keywords: *Evoked Potentials, Auditory, Brain Stem/ph [Physiology]; *Hearing Disorders/di [Diagnosis]; Adolescent; Auditory brainstem response; Auditory evoked potentials; Auditory processing disorders; Child; Evoked Potentials, Auditory, Brain Stem; Female; Hearing Disorders; Hearing Disorders/ep [Epidemiology]; Hearing Tests; Humans; Male; Maximum length sequences; Random Allocation; Speech Perception; Speech Perception/ph [Physiology]; Time Factors; adolescent; age; article; child; clinical article; comparative study; controlled study; dept.cmd; evoked brain stem auditory response; female; gender; hearing impairment; human; intelligence; latent period; male; medical assessment; peer-reviewed; priority journal; sensory system electrophysiology; waveform

Identification of Conductive Hearing Loss in Young Infants Using Tympanometry and Wideband Reflectance. - Prieve, Beth; Vander Werff, Kathy; Preston, Jonathan; Georgantas, Lea (Ear and Hearing, 2013)
Objective: The goal of the study was to evaluate the effectiveness of tympanometry and wideband reflectance (WBR) in detecting conductive hearing loss (CHL) in young infants., Methods: Type of hearing loss was determined using auditory brainstem response using air- and bone-conducted tone bursts in 84 ears from 70 infants (median age = 10 weeks). Of these 84 ears, 60 are included in the current analysis: 43 with normal hearing (NH) and 17 with CHL. Tympanometry was measured using probe tone frequencies of 226, 678, and 1000 Hz. Tympanograms were evaluated in two ways: (1) Acoustic middle ear admittance (Ya, in millimhos); and (2) two-category classification (normal/abnormal), as described by Baldwin (2006). Measures of Ya were evaluated in two ways: by admittance-magnitude tympanograms and calculated admittance magnitude from subcomponents (conductance and susceptance). WBR was measured in response to a chirp stimulus after probe calibration. WBR was analyzed into thirteen 1/3 octave bands. Tests for statistical differences for two-category classification were analyzed using Chi-squared and Ya, and WBR were analyzed using repeated-measures analyses of variances. Cohen's d and likelihood ratios were computed for comparison with statistically significant differences., Results: Ya measured with 678- and 1000 Hz probe tones was significantly different between ears with CHL and NH. Two-category classification of tympanograms using a 1000 Hz probe tone was significantly different between ears with CHL and NH. Neither two-category classification nor Ya was significantly different between ears identified with CHL and NH using a 226 Hz probe tone. WBR was significantly higher in the frequency bands 800 to 2500 Hz and in the frequency band centered at 6300 Hz in infants with CHL. Effect sizes (Cohen's d) were greater than 2 for several WBR frequency bands and Ya measured with 1000 Hz probe tones. The results were similar for calculations of Ya from admittance-magnitude and subcomponent tympanograms. Positive likelihood ratios for WBR ranged between 8.1 and 38, and those for Ya using 1000 Hz ranged between 12.5 and 32., Conclusions: CHL in young infants can be detected well with WBR or tympanometry using probe frequencies of 678 and 1000 Hz., (C) 2013 by Lippincott Williams & Wilkins
Keywords: Acoustic Impedance Tests; Acoustic Stimulation; Evoked Potentials, Auditory, Brain Stem; Female; Hearing Loss, Conductive; Hearing Tests; Humans; Infant; Infant, Newborn; Likelihood Functions; Male; Sensitivity and Specificity; acoustic impedance; article; auditory stimulation; conduction deafness; dept.cmd; evoked brain stem auditory response; female; hearing test; human; infant; male; methodology; newborn; sensitivity and specificity; statistical model

"Putting things in context": Literal and discourse approaches to comprehension assessment - Paul, R. (Seminars in Speech and Language, 2000)
Research on receptive language development in typical children, especially as explicated in a classic paper by Robin Chapman, is reviewed. These findings raise three challenges for clinicians assessing comprehension in children with language disorders: (1) contrary to popular wisdom, comprehension does not always precede production in a simple step-by-step way; (2) comprehension is a private event; indicators of comprehension must be used to assess it, and these indicators can be misleading; and (3) children with subtle comprehension deficits may do well on standardized tests that are not sensitive to their difficulties with real-time discourse. Some strategies for addressing these challenges, as well as a framework for assessing comprehension, are offered.
Keywords: *Child Language; *Cognition; *Language Tests; *Verbal Behavior; Child Language; Child, Preschool; Cognition; Comprehension assessment; Comprehension deficits; Comprehension stages; Discourse comprehension; Humans; Language Tests; Verbal Behavior; article; cognition; dept.cmd; human; language development; language test; preschool child; verbal behavior

Correction to: Abnormalities of aspiration and swallowing function in survivors of acute respiratory failure - Langmore, Susan E.; Krisciunas, Gintas P.; Warner, Heather L.; White, S. David; Dvorkin, Daniel; Fink, Daniel S.; McNally, Edel; Scheel, Rebecca; Higgins, Carrie; Levitt, Joseph E.; McKeehan, Jeffrey; Deane, Sandra; et al. (Dysphagia, 2021)
Due to the errors occurred in the originally published version, this article is being reprinted in its entirety as Correction. All errors have been corrected. It is the correct version. © 2021, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: dept.cmd; erratum; peer-reviewed

Empirical insights into college students’ academic reading comprehension in the united states - Kalbfleisch, Elizabeth; Schmitt, Elena; Zipoli, Richard P. (Journal of College Reading and Learning, 2021)
This article reports on a collaborative research project involving faculty in writing studies, communication disorders, and applied linguistics that sought to empirically describe the reading skills of students (N = 910) in freshman composition classes at one college and two universities in the northeast United States. The research team developed and administered a questionnaire that evaluated students’ reading abilities according to six categories: inferential ability, background knowledge, general comprehension, vocabulary, figurative language/jargon, and morphosyntactic structures (grammar/syntax). Our statistically significant results showed that students scored best in the categories of background knowledge and general comprehension, which are well researched in a college population. However, students struggled in categories such as figurative language/jargon and morpho-syntactic structures, which are not well researched in a college population. Further, comprehension seemed generally discrete (understanding specific points of an essay) rather than holistic (indicated by an ability synthesize those points into a general statement about the author’s thesis). These findings suggest that further empirical research in this area will help describe the reading skills of college students and consequently will inform the development of pedagogical approaches that more effectively address students’ current needs. © 2021 College Reading and Learning Association.
Keywords: dept.cmd; dept.eng; dept.wll; peer-reviewed

The Association Between Endotracheal Tube Size and Aspiration (During Flexible Endoscopic Evaluation of Swallowing) in Acute Respiratory Failure Survivors - Krisciunas, Gintas P.; Langmore, Susan E.; Gomez-Taborda, Stephanie; Fink, Daniel; Levitt, Joseph E.; McKeehan, Jeffrey; McNally, Edel; Scheel, Rebecca; Rubio, Alix C.; Siner, Jonathan M.; Vojnik, Rosemary; Warner, Heather; et al. (Critical Care Medicine, 2020)
Objectives: To determine whether a modifiable risk factor, endotracheal tube size, is associated with the diagnosis of postextubation aspiration in survivors of acute respiratory failure. Design: Prospective cohort study. Setting: ICUs at four academic tertiary care medical centers. Patients: Two hundred ten patients who were at least 18 years old, admitted to an ICU, and mechanically ventilated with an endotracheal tube for longer than 48 hours were enrolled. Interventions: Within 72 hours of extubation, all patients received a flexible endoscopic evaluation of swallowing examination that entailed administration of ice, thin liquid, thick liquid, puree, and cracker boluses. Patient demographics, treatment variables, and hospital outcomes were abstracted from the patient's medical records. Endotracheal tube size was independently selected by the patient's treating physicians. Measurements and Main Results: For each flexible endoscopic evaluation of swallowing examination, laryngeal pathology was evaluated, and for each bolus, a Penetration Aspiration Scale score was assigned. Aspiration (Penetration Aspiration Scale score ≥ 6) was further categorized into nonsilent aspiration (Penetration Aspiration Scale score = 6 or 7) and silent aspiration (Penetration Aspiration Scale score = 8). One third of patients (n = 68) aspirated (Penetration Aspiration Scale score ≥ 6) on at least one bolus, 13.6% (n = 29) exhibited silent aspiration, and 23.8% (n = 50) exhibited nonsilent aspiration. In a multivariable analysis, endotracheal tube size (≤ 7.5 vs ≥ 8.0) was significantly associated with patients exhibiting any aspiration (Penetration Aspiration Scale score ≥ 6) (p = 0.016; odds ratio = 2.17; 95% CI 1.14-4.13) and with risk of developing laryngeal granulation tissue (p = 0.02). Conclusions: Larger endotracheal tube size was associated with increased risk of aspiration and laryngeal granulation tissue. Using smaller endotracheal tubes may reduce the risk of postextubation aspiration. © 2020 International Anesthesia Research Society.
Keywords: Adult; Aged; Airway extubation; Deglutition; Deglutition disorders; Female; Humans; Intensive Care Units; Intratracheal intubation; Intubation, Intratracheal; Male; Middle Aged; Prospective Studies; Respiration, Artificial; Respiratory Aspiration; Respiratory Insufficiency; Respiratory aspiration; Respiratory distress syndrome; Risk Factors; Survivors; acid aspiration; adverse event; aged; artificial ventilation; clinical trial; dept.cmd; devices; endotracheal intubation; female; human; intensive care unit; male; middle aged; multicenter study; peer-reviewed; physiology; procedures; prospective study; respiratory failure; risk factor; survivor; swallowing

Development of an Accurate Bedside Swallowing Evaluation Decision Tree Algorithm for Detecting Aspiration in Acute Respiratory Failure Survivors - Moss, Marc; White, S. David; Warner, Heather; Dvorkin, Daniel; Fink, Daniel; Gomez-Taborda, Stephanie; Higgins, Carrie; Krisciunas, Gintas P.; Levitt, Joseph E.; McKeehan, Jeffrey; McNally, Edel; Rubio, Alix; et al. (Chest, 2020)
Background: The bedside swallowing evaluation (BSE) is an assessment of swallowing function and airway safety during swallowing. After extubation, the BSE often is used to identify the risk of aspiration in acute respiratory failure (ARF) survivors. Research Question: We conducted a multicenter prospective study of ARF survivors to determine the accuracy of the BSE and to develop a decision tree algorithm to identify aspiration risk. Study Design and Methods: Patients extubated after ≥ 48 hours of mechanical ventilation were eligible. Study procedures included the BSE followed by a gold standard evaluation, the flexible endoscopic evaluation of swallowing (FEES). Results: Overall, 213 patients were included in the final analysis. Median time from extubation to BSE was 25 hours (interquartile range, 21-45 hours). The FEES was completed 1 hour after the BSE (interquartile range, 0.5-2 hours). A total of 33% (70/213; 95% CI, 26.6%-39.2%) of patients aspirated on at least one FEES bolus consistency test. Thin liquids were the most commonly aspirated consistency: 27% (54/197; 95% CI, 21%-34%). The BSE detected any aspiration with an accuracy of 52% (95% CI, 45%-58%), a sensitivity of 83% (95% CI, 74%-92%), and negative predictive value (NPV) of 81% (95% CI, 72%-91%). Using recursive partitioning analyses, a five-variable BSE-based decision tree algorithm was developed that improved the detection of aspiration with an accuracy of 81% (95% CI, 75%-87%), sensitivity of 95% (95% CI, 90%-98%), and NPV of 97% (95% CI, 95%-99%). Interpretation: The BSE demonstrates variable accuracy to identify patients at high risk for aspiration. Our decision tree algorithm may enhance the BSE and may be used to identify patients at high risk for aspiration, yet requires further validation. Trial Registry: ClinicalTrials.gov; No.: NCT02363686; URL: www.clinicaltrials.gov; © 2020 American College of Chest Physicians
Keywords: Airway Extubation; Algorithms; Article; Decision Trees; Deglutition; Female; Humans; Male; Point-of-Care Testing; Predictive Value of Tests; Reproducibility of Results; Respiration, Artificial; Respiratory Aspiration; Respiratory Insufficiency; Risk Assessment; Survivors; Symptom Assessment; United States; acid aspiration; acute respiratory failure; adult; adverse event; aged; algorithm; artificial ventilation; aspiration; bedside swallowing evaluation; clinical trial; controlled study; decision tree; dept.cmd; diagnostic accuracy; diagnostic test accuracy study; digestive system examination; dysphagia; epidemiology; extubation; female; flexible endoscopic evaluation of swallowing; gastrointestinal endoscopy; high risk patient; human; intubation; major clinical study; male; multicenter study; oxygen; oxygen therapy; pathophysiology; peer-reviewed; point of care testing; predictive value; priority journal; procedures; prospective study; pulmonary aspiration; reproducibility; respiratory failure; risk assessment; sensitivity and specificity; speech language pathologist; survivor; swallowing; symptom assessment

Transdisciplinary Approach Practicum for Speech-Language Pathology and Special Education Graduate Students - Weiss, Deborah; Cook, Barbara; Eren, Ruth (Journal of Autism and Developmental Disorders, 2020)
Speech-language pathology and special education graduate student teams participated in an intensive summer practicum for social communication skills with children with autism spectrum disorders, utilizing a transdisciplinary approach that aligned to the frameworks utilized for implementation science. Questionnaires measuring transdisciplinary approach knowledge and comfort level were administered pre/post-practicum. Results of the questionnaires, written daily team reflections, course evaluations, and a focus group interview indicated an increase in all measures, including an increased knowledge of TA, increased understanding and comfort level with the other discipline, and a higher level of confidence and openness in working collaboratively utilizing a transdisciplinary approach. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Academic Performance; Article; Autism Spectrum Disorder; Autism spectrum disorder; Child; Collaborative teaming; Communication; Education, Special; Female; Humans; Implementation science; Interdisciplinary Research; Interprofessional collaboration; Male; Special education; Speech-Language Pathology; Speech-language pathology; Students, Health Occupations; Surveys and Questionnaires; Transdisciplinary; academic achievement; autism; child; comfort; communication skill; course evaluation; dept.cmd; dept.sed; education; female; graduate student; health student; human; implementation science; interdisciplinary education; interdisciplinary research; interpersonal communication; interview; knowledge; male; peer-reviewed; pretest posttest design; priority journal; procedures; professional development; psychology; quantitative analysis; questionnaire; social competence; special education; speech disorder; teacher; training

Abnormalities of Aspiration and Swallowing Function in Survivors of Acute Respiratory Failure - Langmore, Susan E.; Krisciunas, Gintas P.; Warner, Heather; White, S. David; Dvorkin, Daniel; Fink, Daniel; McNally, Edel; Scheel, Rebecca; Higgins, Carrie; Levitt, Joseph E.; McKeehan, Jeffrey; Deane, Sandra; et al. (Dysphagia, 2020)
The mechanisms responsible for aspiration are relatively unknown in patients recovering from acute respiratory failure (ARF) who required mechanical ventilation. Though many conditions may contribute to swallowing dysfunction, alterations in laryngeal structure and swallowing function likely play a role in the development of aspiration. At four university-based tertiary medical centers, we conducted a prospective cohort study of ARF patients who required intensive care and mechanical ventilation for at least 48 h. Within 72 h after extubation, a Fiberoptic Flexible Endoscopic Evaluation of Swallowing (FEES) examination was performed. Univariate and multivariable analyses examined the relationship between laryngeal structure and swallowing function abnormalities. Aspiration was the primary outcome, defined as a Penetration- Aspiration Scale (PAS) score of 6 or greater. Two other salient signs of dysphagia—spillage and residue—were secondary outcomes. A total of 213 patients were included in the final analysis. Aspiration was detected in 70 patients (33%) on at least one bolus. The most commonly aspirated consistency was thin liquids (27%). In univariate analyses, several abnormalities in laryngeal anatomy and structural movement were significantly associated with aspiration, spillage, and residue. In a multivariable analysis, the only variables that remained significant with aspiration were pharyngeal weakness (Odds ratio = 2.57, 95%CI = 1.16–5.84, p = 0.019) and upper airway edema (Odds ratio = 3.24, 95%CI = 1.44–7.66, p = 0.004). These results demonstrated that dysphagia in ARF survivors is multifactorial and characterized by both anatomic and physiologic abnormalities. These findings may have important implications for the development of novel interventions to treat dysphagia in ARF survivors. Clinical Trials Registration ClinicalTrials.gov Identifier: NCT02363686, Aspiration in Acute Respiratory FailureSurvivors. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Deglutition; Deglutition Disorders; Humans; Prospective Studies; Respiratory Aspiration; Respiratory Insufficiency; Survivors; acid aspiration; dept.cmd; dysphagia; human; peer-reviewed; prospective study; respiratory failure; survivor; swallowing

Evidence-based practice among speech-language pathologists: attitudes, utilization, and barriers. - Zipoli, Richard P Jr; Kennedy, Marianne (American Journal of Speech-language Pathology, 2005)
A total of 240 speech-language pathologists responded to a questionnaire examining attitudes toward and use of research and evidence-based practice (EBP). Perceived barriers to EBP were also explored. Positive attitudes toward research and EBP were reported. Attitudes were predicted by exposure to research and EBP practice during graduate training and the clinical fellowship year (CFY). Clinical experience and opinions of colleagues were used to guide decision making more frequently than research studies or clinical practice guidelines. Only exposure to research and EBP during the CFY predicted use of evidence-based resources. Respondents reported a decline in exposure to research and EBP as they moved from graduate training into the CFY. A lack of time was perceived as a barrier to EBP.
Keywords: *Attitude of Health Personnel; *Data Collection/sn [Statistics & Numerical Data]; *Evidence-Based Medicine; *Health Knowledge, Attitudes, Practice; *Speech-Language Pathology/st [Standards]; Clinical fellowship; Evidence-based practice; Humans; Practice issues; Research; Speech-Language Pathology/sn [Statistics & Numerical Data]; Speech-language pathology; Surveys and Questionnaires; United States; dept.cmd

Educating and training caregivers of persons with aphasia - Purdy, Mary; Hindenlang, Jane (Aphasiology, 2005)
Background: Because communication deficits caused by aphasia affect both persons with aphasia and their communication partners, most speech-language pathologists are aware of the importance of client and caregiver education. To maximise the effectiveness of their communicative interactions, training should be conducted for both the aphasic clients and their caregivers. Training conducted in group environments offers peer support through shared learning experiences and joint problem solving. Aims: The purpose of this study was to explore the benefits of a caregiver education and training programme in improving communication between caregivers and their aphasic partners using didactic and experiential approaches in a group setting. Methods & procedures: Ten caregivers and their aphasic partners, ranging from 4 to 130 months post-stroke, participated in a 12-week group training and education programme. Information about stroke and aphasia was provided in a didactic format, and facilitative communication strategies were discussed and practised using Kolb's (1984) experiential learning cycle model. The experiential learning cycle involved drawing on concrete experiences, engaging in reflective observation and abstract conceptualisation, and practising what was learned through active experimentation. Outcomes & results: Analysis of communicative performance on transactional and interactional tasks demonstrated increased communicative success. Responses on a questionnaire indicated that participants had a better understanding of aphasia and were more confident using facilitating strategies. Conclusions: Group education and training for caregivers and their aphasic partners can be beneficial, even after the couple has been living with aphasia for a number of years. Having an opportunity to practise, observe, and reflect on their performances facilitated participants' learning, and there were observed and reported positive alterations in interactions. © 2005 Psychology Press Ltd.
Keywords: adult; aged; aphasia; article; caregiver; cerebrovascular accident; clinical article; cognition; dept.cmd; disease severity; education program; experience; female; group therapy; health education; human; information dissemination; interpersonal communication; learning; male; medical education; patient education; peer-reviewed; problem solving; questionnaire; self concept; social support; task performance

Perception and Production of Prosody by Speakers with Autism Spectrum Disorders. - Paul, Rhea; Augustyn, Amy; Klin, Ami; Volkmar, Fred R (Journal of Autism and Developmental Disorders, 2005)
Speakers with autism spectrum disorders (ASD) show difficulties in suprasegmental aspects of speech production, or prosody, those aspects of speech that accompany words and sentences and create what is commonly called "tone of voice." However, little is known about the perception of prosody, or about the specific aspects of prosodic production that result in the perception of "oddness." The present study examined the perception and production of a range of specific prosodic elements in an experimental protocol involving natural speech among speakers with ASD between 14 and 21 years of age, in comparison with a typical control group. Results revealed ceiling effects limiting interpretation of findings for some aspects of prosody. However, there were significant between-group differences in aspects of stress perception and production. The implications of these findings for understanding prosodic deficits is speakers with autism spectrum disorders, and for future research in this area, are discussed.
Keywords: *Autistic Disorder/co [Complications]; *Language Disorders/et [Etiology]; *Perceptual Disorders/et [Etiology]; *Phonetics; *Speech Disorders/et [Etiology]; *Speech Perception; Adolescent; Adult; Autism; Autistic Disorder; Humans; Language; Language Disorders; Language Disorders/di [Diagnosis]; Language Tests; Male; Perceptual Disorders; Perceptual Disorders/di [Diagnosis]; Phonetics; Prosody; Speech Discrimination Tests; Speech Disorders; Speech Disorders/di [Diagnosis]; Speech Perception; Speech Production Measurement; article; autism; child; clinical article; clinical protocol; controlled study; correlation analysis; dept.cmd; human; intelligence quotient; intermethod comparison; language; medical assessment; peer-reviewed; perception; priority journal; prosody; reliability; scoring system; speech; speech disorder; statistical significance; stress; task performance

Communication quality indicators: A survey of connecticut group home managers - Desimone, Evelyn A; Cascella, Paul W (Journal of Developmental and Physical Disabilities, 2005)
Thirty-one Connecticut group home managers responded to a 23-statement survey adapted from the Communications Supports Checklist for Programs Serving Individuals with Severe Disabilities (CSC; McCarthy et al., 1998, Paul H. Brookes, Baltimore, MD.). Results indicated that group home managers had very favorable opinions about the implementation of communication quality indicators in their group homes, and the degree of a resident's intellectual disability was not a factor in communication supports implementation. Three communication quality indicators were rated especially high: program philosophy, protection of communication rights, and assessment. Environmental support for communication was rated less favorably. Follow-up interviews with seven group home managers found that they especially valued direct care staff who understood a resident's idiosyncratic communication (e.g., response sensitivity). Managers also relied on team process for referral for ongoing speech-language consultation. Results from the surveys and interviews indicated that augmentative communication applications occurred less often than other quality communication indicators.
Keywords: Communication supports; Group home; Severe disabilities; dept.cmd; peer-reviewed

Gin (gaps-in-noise) test performance in subjects with confirmed central auditory nervous system involvement - Musiek, Frank E; Shinn, Jennifer B; Jirsa, Robert E; Bamiou, Doriseva; Baran, Jane A; Zaida, Elena (Ear and Hearing, 2005)
OBJECTIVE: The purpose of the present study was to investigate the value of a new gap detection procedure called Gaps-In-Noise (GIN) for assessment of temporal resolution in a clinical population. DESIGN: The test consists of 0 to 3 silent intervals ranging from 2 to 20 msec embedded in 6-sec segments of white noise. The location, number, and duration of the gaps per noise segment vary throughout the test for a total of 60 gaps presented in each of four lists. The GIN procedure was administered to 50 normal-hearing listeners (group I) and 18 subjects with confirmed neurological involvement of the central auditory nervous system (group II). RESULTS: Results showed mean approximated gap detection thresholds of 4.8 msec for the left ear and 4.9 msec for the right ear for group I. In comparison, results for group II demonstrated a statistically significant increase in gap detection thresholds, with approximated thresholds of 7.8 msec and 8.5 msec being noted for the left and right ears, respectively. Significant mean differences were also observed in the overall performance scores (i.e., the identification of the presence of the gaps within the noise segments) of the two groups of subjects. Finally, psychometric functions, although similar for short and long duration gaps, were highly different for gaps in the 4- to 10-msec range for the two groups. CONCLUSIONS: A variety of psychoacoustic procedures are available to assess temporal resolution; however, the clinical use of these procedures is minimal at best. Results of the present study show that the GIN test holds promise as a clinically useful tool in the assessment of temporal resolution in the clinical arena. Copyright © 2005 by Lippincott Williams & Wilkins.
Keywords: Adolescent; Adult; Aged; Aneurysm; Auditory Diseases, Central; Auditory Threshold; Case-Control Studies; Cerebrovascular Accident; Electrophysiology; Evoked Potentials, Auditory; Female; Humans; Male; Middle Aged; Noise; Perceptual Masking; Reaction Time; Reproducibility of Results; Stroke; adolescent; adrenoleukodystrophy; adult; article; auditory nervous system; brain artery aneurysm; clinical article; controlled study; dept.cmd; false positive result; female; gaps in noise test; hearing; hemispheric dominance; human; learning disorder; male; noise; pitch; psychometry; psychophysics; pure tone audiometry; receiver operating characteristic; stroke; temporal summation; test retest reliability; white noise

Brief Report: Relations between Prosodic Performance and Communication and Socialization Ratings in High Functioning Speakers with Autism Spectrum Disorders. - Paul, Rhea; Shriberg, Lawrence; McSweeny, Jane; Cicchetti, Domenic; Klin, Ami; Volkmar, Fred (Journal of Autism and Developmental Disorders, 2005)
Shriberg et al. [ Shriberg, L. et al. (2001). Journal of Speech, Language and Hearing Research, 44, 1097-1115] described prosody-voice features of 30 high functioning speakers with autistic spectrum disorder (ASD) compared to age-matched control speakers. The present study reports additional information on the speakers with ASD, including associations among prosody-voice variables and ratings of communication social abilities. Results suggest that the inappropriate sentential stress and hypernasality previously identified in some of these speakers is related to communication/sociability ratings. These findings and associated trends are interpreted to indicate important links between prosodic performance and social and communicative competence. They suggest the need for careful assessment of inappropriate prosody and voice features in speakers with ASD, and for effective intervention programs aimed at reducing the stigmatization of individuals with these conditions., (C) Plenum Publishing Corporation 2005. All Rights Reserved.
Keywords: Adolescent; Adult; Asperger syndrome; Autism; Autistic Disorder; Communication; Female; Humans; Male; Middle Aged; Prosody; Severity of Illness Index; Socialization; Speech; Speech Production Measurement; Voice Quality; adolescent; adult; article; autism; child; clinical article; communication; communication skill; controlled study; dept.cmd; female; hospitalization; human; human experiment; interpersonal communication; linguistics; male; middle aged; nasal speech; peer-reviewed; priority journal; prosody; social adaptation; social psychology; socialization; speech; speech analysis; speech disorder; verbal communication; voice

Discharge Practices in the University Clinical Setting - McNamara, Kevin M.; Hindenlang, Jane; Cascella, Paul W. (Contemporary Issues in Communication Science and Disorders, 2004)
This study investigated the degree to which clinic directors rated the influence of American Speech-Language-Hearing Association (ASHA) discharge criteria and organizational factors on client discharge in the university setting. Results found that university clinic directors regarded ASHA's client-centered criteria to more strongly influence client discharge practices than did organizational factors. In fact, organizational factors (e.e., fee structure, resources, scheduling, disorder characteristics) were revealed to have little to no influence on discharge practices. Results have implications for the pre-professional education of student clinicians in the university clinic and how student clinicians are oriented to discharge practices across a variety of clinical settings.
Keywords: dept.cmd

Pediatricians' opinions about otitis media and speech-language-hearing development - Sonnenschein, Esther; Cascella, Paul W (Journal of Communication Disorders, 2004)
Twenty-five pediatricians responded to a confidential survey about their opinions on the relationship between otitis media and children's speech-language-hearing status. Results found that pediatricians did not necessarily agree that otitis media has an impact on speech-language-hearing development. Pediatricians reported that an early otitis media onset (birth to age 2) affects speech-language development, but they also reported that parents and daycare environments could mitigate any otitis media effect. Pediatricians reported a possible otitis media impact on hearing status, but they did not necessarily agree that an otitis media history required referral for audiological testing. Clinical implications are discussed for collaboration among pediatricians, speech-language pathologists, and audiologists. Learning outcomes: (1) The reader will become familiar with pediatricians' opinions about the impact of otitis media on speech-language development. (2) The reader will become familiar with strategies to support interdisciplinary collaboration between pediatricians, speech-language pathologists, and audiologists. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: *Attitude to Health; *Hearing Disorders/ep [Epidemiology]; *Language Disorders/ep [Epidemiology]; *Otitis Media/ep [Epidemiology]; *Pediatrics; *Speech Disorders/ep [Epidemiology]; Child; Humans; Medical practices; Otitis media; Pediatricians; Speech-language development; dept.cmd; health survey; hearing; human; language development; medical practice; otitis media; pediatrician; questionnaire; review; speech development; thinking

Receptive communication abilities among adults with significant intellectual disability - Cascella, Paul W (Journal of Intellectual & Developmental Disability, 2004)
This study measured the receptive communication skills of 14 adults with significant intellectual disability living in community group homes in Connecticut. Group home staff members rated the 14 participants using it 14-item rating scale sensitive to the adult living situation. These individuals appeared to have relatively stronger skills for comprehension of single-step in-context directions and the ability to recognise that particular tangible objects represented certain daily routines. These individuals were relatively, weak in identifying,familiar people in photographs and common objects in magazines. Among these participants, persons with profound intellectual disability mere rated to hate lower receptive communication skills than persons with severe intellectual disability. Clinical implications are discussed for human service providers and education professionals.
Keywords: Down syndrome; adult; anxiety disorder; article; clinical article; depression; dept.cmd; developmental disorder; disability; disease severity; female; hearing loss; human; interpersonal communication; male; mental disease; psychosis; scoring system; seizure

Knowledge of autism spectrum disorders among connecticut school speech-language pathologists. - Cascella, Paul W; Colella, Catherine S (Focus on Autism and Other Developmental Disabilities, 2004)
This study utilized a rating scale and random sampling of Connecticut school speech—language pathologists about their preprofessional education and current knoWledge of autism spectrum disorders (ASD). The participants had a minimal amount of preprofessional academic or clinical preparation in ASD, and no differences Were found in hoW speech—language pathologists Were trained over the past 30 years. School speech—language pathologists reported relatively stronger knoWledge of the general behavioral and communication characteristics associated With ASD and less knoWledge of educational assessment and intervention formats. Given the prevalence of schoolchildren With ASD, speech—language pathology graduate programs need to enhance their preprofessional curricula to provide school-based speech—language pathologists With specific training to meet the communication needs presented by children With ASD. © 2004, Sage Publications. All rights reserved.
Keywords: dept.cmd

Adaptive behavior in autism and pervasive developmental disorder-not otherwise specified: Microanalysis of scores on the vineland adaptive behavior scales - Paul, R.; Miles, S.; Cicchetti, D.; Sparrow, S.; Klin, A.; Volkmar, F.; Coflin, M.; Booker, S. (Journal of Autism and Developmental Disorders, 2004)
The purpose of this study is to provide a microanalysis of differences in adaptive functioning seen between well-matched groups of school-aged children with autism and those diagnosed as having Pervasive Developmental Disorder-Not Otherwise Specified, all of whom functioned in the mild to moderate range of intellectual impairment. Findings indicate that the major area of difference between children with autism and those with Pervasive Developmental Disorder-Not Otherwise Specified, was expressive communication; specifically, the use of elaborations in syntax and morphology and in pragmatic use of language to convey and to seek information in discourse. Linear discriminant function analysis revealed that scores on just three of these expressive communication item sets correctly identified subjects in the two diagnostic categories with 80% overall accuracy. Implications of these findings for both diagnosis and intervention with children with Autism Spectrum Disorders will be discussed.
Keywords: Activities of Daily Living; Adaptation, Psychological; Adaptive behavior; Autism; Autistic Disorder; Child; Child Development Disorders, Pervasive; Child, Preschool; Communication; Discriminant Analysis; Expressive language; Female; Humans; Personality Tests; Pervasive Developmental Disorders; Social Behavior; Socialization; adaptive behavior; article; autism; brain function; child; clinical article; comparative study; controlled study; dept.cmd; developmental disorder; diagnostic accuracy; diagnostic approach route; female; functional anatomy; human; intellectual impairment; interpersonal communication; language; linear system; male; microanalysis; peer-reviewed; priority journal; rating scale; scoring system; socialization; treatment indication

Promoting social communication in high functioning individuals with autistic spectrum disorders - Paul, Rhea (Child and Adolescent Psychiatric Clinics of North America, 2003)
This article reviews a range of social communication interventions that have been developed for students with autism at the preschool, school age, and adolescent level. Adult-mediated and peer-mediated methods that use highly structured, child-centered, and hybrid methods are examined. Programs that provide information on generalization and maintenance are identified. A set of recommendations for programs that would seem to be most appropriate for students with Asperger syndrome is presented.
Keywords: *Asperger Syndrome/th [Therapy]; *Autistic Disorder/th [Therapy]; *Intelligence; *Social Behavior; Adolescent; Asperger Syndrome/di [Diagnosis]; Asperger Syndrome/px [Psychology]; Asperger syndrome; Autistic Disorder/di [Diagnosis]; Autistic Disorder/px [Psychology]; Behavior Therapy; Child; Child, Preschool; Humans; Peer Group; Play and Playthings; Social Adjustment; adolescent; adult; autism; child; child psychiatry; dept.cmd; human; interpersonal communication; peer-reviewed; priority journal; review; school; social adaptation; social interaction; training; verbal communication

Management of children with APDs - Jirsa, Robert E (The Hearing journal, 2003)
The management of children with auditory processing disorders requires a multifaceted approach involving audiologists, speech-language pathologists, and educators. We are still at the genesis of our understanding of APDs.
Keywords: accuracy; association; audiology; auditory discrimination; auditory nervous system; auditory stimulation; auditory system examination; auditory system function; child; child behavior; child care; computer program; dept.cmd; frequency modulation; health care planning; hearing disorder; human; interpersonal communication; medical specialist; note; school; sensory system electrophysiology; signal noise ratio; signal processing; task performance; technology; writing

Recovery of communication skills following intracerebral hemorrhage: A case study - Purdy, MH (Journal of Medical Speech-Language Pathology, 2001)
Numerous variables contribute to the ultimate recovery of communication skills following neurological damage. This report provides a review of the literature pertaining to prognostic indicators and chronicles the recovery of communication skills in a 48-year-old man who sustained a left intracerebral hemorrhage over a 29-month period.
Keywords: adult; article; brain hemorrhage; case report; communication disorder; dept.cmd; human; male; priority journal; prognosis; skill; speech rehabilitation; treatment outcome; ⛔ No DOI found

Psycholinguistic models of speech development and their application to clinical practice - Baker, Elise; Croot, Karen; Mcleod, Sharynne; Paul, Rhea (Journal of Speech Language and Hearing Research, 2001)
This article presents an introduction to psycholinguistic models of speech development. Two specific types of models are addressed: box-and-arrow models and connectionist or neural network models. We review some historical and some current models and discuss recent applications of such models to the management of speech impairment in children. We suggest that there are two ways in which a psycholinguistic approach can influence clinical practice: by directly supplementing a speech-language pathologist's repertoire of assessment and treatment approaches and by offering a new way to conceptualize speech impairment in children.
Keywords: Assessment; Brain; Child Language; Child, Preschool; Connectionist models; Humans; Impairment; Language Disorders; Neural Networks (Computer); Psycholinguistic models; Psycholinguistics; Speech; Speech development; Verbal Learning; article; artificial neural network; brain; dept.cmd; human; language development; language disability; learning; linguistics; pathophysiology; preschool child; speech

TBI knowledge and pragmatic assessment among Connecticut school speech-language pathologists - McGrane, S.A.; Cascella, P.W. (Brain Injury, 2000)
School-based speech-language pathologists from Connecticut responded to a random survey which had a twofold purpose, (1) to replicate a previous conclusion that clinicians' specific experience with traumatic brain injury (TBI) influences their knowledge of this subject, and (2) to explore the topic of pragmatic assessment and whether it is also influenced by specific TBI experience. Results indicate that Connecticut school clinicians favourably regard both their own knowledge of TBI and the contemporary issue of pragmatic assessment. Connecticut clinicians also report a relatively low degree of prior TBI training and clinical experience. Clinicians' degree of TBI training and clinical experience did not appear directly related to their reported competence in TBI knowledge and pragmatic assessment.
Keywords: *Brain Injuries/di [Diagnosis]; *Professional Competence; *Self-Assessment; *Speech-Language Pathology/ed [Education]; Adult; Connecticut; Female; Humans; Male; Middle Aged; Schools; Surveys and Questionnaires; Workforce; article; brain injury; competence; dept.cmd; education; experience; functional assessment; human; linguistics; normal human

Fundamental frequency and gender identification in standard esophageal and tracheoesophageal speakers. - Bellandese, Mary H (Journal of Communication Disorders, 2009)
UNLABELLED: The purpose of this study was to determine if there was a relationship between fundamental frequency (Fo) and gender identification in standard esophageal (ES) or tracheoesophageal (TE) speakers. Twenty-three male and 20 female ES and TE speakers participated in this study. Recordings of these speakers reading the Rainbow Passage were played to 48 listeners who indicated perceived gender in a forced choice format. Fo was determined using PC-AUDED [Boston University (1991). Using PC-AUDED, Audio-editor and analyses program for the study of periodic segments. Boston: Boston University]. Seventy-nine percent of the speakers were identified correctly for gender. No significant difference was found between the number of male and female or TE and ES speakers identified correctly. A significant correlation was found between Fo and correct gender identification for the female speakers only. Results suggest that Fo plays a part in gender identification for female SE and TE speakers, however, other factors may also be important cues for gender identification in these speakers., LEARNING OUTCOMES: As a result of this activity, the participant will be able to: (1) describe the relationship between Fo and gender identification for male and female standard esophageal (SE) and tracheoesophageal (TE) speakers (2) discuss other variables that may influence gender identification in SE and TE speakers.
Keywords: *Sex Characteristics; *Speech Acoustics; *Speech Perception; *Speech, Esophageal/px [Psychology]; *Trachea; Adult; Aged; Aged, 80 and over; Female; Humans; Male; Middle Aged; Sex Characteristics; Sound Spectrography; Speech Acoustics; Speech Perception; Speech, Esophageal; Task Performance and Analysis; Trachea; Young Adult; dept.cmd

Conversational Behaviors in Youth with High-functioning ASD and Asperger Syndrome. - Paul, Rhea; Orlovski, Stephanie; Marcinko, Hillary; Volkmar, Fred (Journal of Autism and Developmental Disorders, 2009)
Twenty-nine youth with autism spectrum disorders and 26 with typical development between 12 and 18 years of age were engaged in structured interviews (ADOS). The interviews were videotaped and rated for atypical conversational behaviors by trained raters, using the Pragmatic Rating Scale (Landa et al. Psychol Med 22:245-254, 1992). The ASD group was divided into AS and HFA/PDD-NOS subgroups. Significant differences were found among groups on approximately one-third of the PRS items. These items involved primarily the management of topics and information, reciprocity, intonation, and gaze management. The only differences to reach significance between the AS and HFA/PDD-NOS group were a greater tendency for overly formal speech on the part of the AS group, and more difficulty with gaze management on the part of the group with HFA/PDD-NOS. The implications of these findings for understanding and treating conversational deficits in ASD are discussed., (C) Plenum Publishing Corporation 2009. All Rights Reserved.
Keywords: *Asperger Syndrome/di [Diagnosis]; *Autistic Disorder/di [Diagnosis]; *Interpersonal Relations; *Verbal Behavior; Adolescent; Asperger Syndrome; Asperger Syndrome/px [Psychology]; Asperger syndrome; Autism; Autistic Disorder; Autistic Disorder/px [Psychology]; Child; Conversation; Female; Humans; Intelligence; Interpersonal Relations; Keywords; Language Development Disorders; Language Development Disorders/di [Diagnosis]; Language Development Disorders/px [Psychology]; Male; Pragmatics; Pragmatics Conversation; Speech Acoustics; Speech Intelligibility; Verbal Behavior; Vocabulary; article; autism; behavior; clinical article; controlled study; conversation; dept.cmd; human; juvenile; peer-reviewed; priority journal; rating scale; structured interview; videotape

Language outcomes of toddlers with autism spectrum disorders: A two year follow-up - Paul, Rhea; Chawarska, Katarzyna; Cicchetti, Domenic; Volkmar, Fred (Autism Research, 2008)
Thirty-seven children 15-25 months of age received clinical diagnoses of autism spectrum disorder (ASD) and were re-evaluated two years later. All subjects were judged to have retained a diagnosis of ASD at the follow-up evaluation. Communication scores for the group as a whole during the first visit were significantly lower than nonverbal IQ. However, by the second visit, verbal and nonverbal scores were no longer significantly different. The group was divided into two subgroups, based on expressive language (EL) outcome at the second visit. The two groups were similar in the second year of life in terms of expressive communication skills and autistic symptoms, except for a trend toward more stereotypic and repetitive behavior in the worse outcome group. By the second visit, however, the groups differed significantly on all standard measures of expression and reception, as well as on autistic symptomotology and nonverbal IQ. When assessed during their second year, children who ended up in the better outcome group showed higher average nonverbal cognitive level, receptive language (RL) scores, number of sounds and words produced, use of symbolic play schemes, and response to joint attention bids. Regression analysis revealed that the variables for which significant differences between the two outcome groups in their second year of life were found provided significant prediction of EL outcome at age four. Stepwise regression identified RL and presence of stereotypic and repetitive at the first visit as significantly associated with EL outcome. Implications of these findings for early identification and intervention are discussed.
Keywords: Autism; Autistic Disorder; Child, Preschool; Communication; Follow-Up Studies; Humans; Infant; Language; Language Disorders; Language Tests; Language Therapy; Observer Variation; Questionnaires; Severity of Illness Index; Toddlers; article; autism; dept.cmd; follow up; hospitalization; human; infant; interpersonal communication; language disability; language test; observer variation; preschool child; questionnaire; speech therapy

Production of syllable stress in speakers with autism spectrum disorders - Paul, Rhea; Bianchi, Nancy; Augustyn, Amy; Klin, Ami; Volkmar, Fred R. (Research in Autism Spectrum Disorders, 2008)
This paper reports a study of the ability to reproduce stress in a nonsense syllable imitation task by adolescent speakers with autism spectrum disorders (ASD), as compared to typically developing (TD) age-mates. Results are reported for both raters' judgments of the subjects' stress production, as well as acoustic measures of pitch range and duration during stressed and unstressed syllable production. Results reveal small but significant differences between speakers with ASD and typical speakers in both perceptual ratings of stress and instrumental measures of duration of syllables. The implications of these findings for understanding prosodic deficits in ASD are discussed. (C) 2007 Elsevier Ltd. All fights reserved.
Keywords: Autism; Prosody; Syllable stress; acoustics; adolescent; adult; article; autism; clinical article; controlled study; dept.cmd; feedback system; female; human; intelligence quotient; male; mental task; motor coordination; pitch; priority journal; school child; speech articulation; speech perception; task performance

Auditory processing disorder - Paul, Rhea (Journal of Autism and Developmental Disorders, 2008)
Keywords: *Auditory Perceptual Disorders/co [Complications]; *Auditory Perceptual Disorders/di [Diagnosis]; *Autistic Disorder/co [Complications]; *Autistic Disorder/di [Diagnosis]; Auditory Perceptual Disorders; Autistic Disorder; Child; Cognition Disorders; Cognition Disorders/co [Complications]; Humans; Male; Speech Perception; audiologist; auditory processing disorder; autism; brain; central nervous system; dept.cmd; ear; editorial; hearing disorder; hearing test; peer-reviewed; priority journal; signal transduction; social interaction; sound transmission; speech

Performance of bilingual speakers on the English and Spanish versions of the Hearing in Noise Test (HINT). - Weiss, Deborah; Dempsey, James J (Journal of the American Academy of Audiology, 2008)
This study compared the performance of bilingual participants on the English and Spanish versions of the Hearing in Noise Test (HINT). The participants were divided into an early bilingual (EB) group and a late bilingual (LB) group based on age of second-language acquisition. All participants acquired Spanish as their first language (L1) and English as a second language (L2). Care was taken to ensure that all participants demonstrated at least a "good competence level" for self-rated speaking, understanding, reading, and writing skills in both English and Spanish. Results revealed superior performance on the Spanish HINT versus the English HINT in both quiet and in noise for both groups of participants. Significant differences in performance were noted for the EB versus the LB participants. A number of possible explanations for superior performance in L1 are provided, and implications for educating students in their L2 are discussed.
Keywords: *Language Tests; *Multilingualism; *Speech Perception/ph [Physiology]; *Verbal Learning/ph [Physiology]; Adolescent; Adult; Age Factors; Bilingual; Child; English as a second language; Female; Hearing; Hearing in Noise Test; Humans; Language Tests; Linguistic competence; Male; Multilingualism; Noise; Regression Analysis; Speech Perception; Speech recognition in noise; Speech recognition in quiet; Students; United States; Verbal Learning; adolescent; adult; article; auditory threshold; bilingualism; controlled study; dept.cmd; education; female; human; language ability; learning environment; linguistics; male; normal human; peer-reviewed; priority journal; school child; self report; signal noise ratio; speech and language assessment; speech intelligibility; speech perception

Eliciting a distal gesture via dynamic assessment among students with moderate to severe intellectual disability - McLaughlin, Katherine; Cascella, Paul W. (Communication Disorders Quarterly, 2008)
This study attempted to elicit distal gestures within dynamic assessment structured sampling events from six children with moderate to severe intellectual disability (ages 8-13). Using four communication temptations and a least-to-most prompting hierarchy across three sessions, three participants who had both pre-symbolic and preintentional communication demonstrated an initial distal gesture, often in response to a choice making temptation. Clinical implications are discussed with regard to the utility of dynamic assessment structured sampling activities. © 2008, SAGE Publications. All rights reserved.
Keywords: dept.cmd

“Listen my children and you shall hear”: Auditory preferences in toddlers with autism spectrum disorders - Paul, Rhea; Chawarska, Katarzyna; Fowler, Carol; Cicchetti, Domenic; Volkmar, Fred (Journal of Speech Language and Hearing Research, 2007)
Purpose: This study tests the hypothesis that toddlers with autism spectrum disorders (ASD) will show differences from contrast groups in preferences for attending to speech. Method: This study examined auditory preferences in toddlers with ASD and matched groups of (a) typical age-mates, (b) age-mates with nonautistic developmental disabilities, and (c) younger children matched for language age. The experimental procedure measured time spent oriented to auditory stimuli that were created to exemplify language patterns that had been studied in typically developing infants. Results: Findings suggest that toddlers with ASD show a reduced preference for child-directed speech, compared with typical age-mates, but few differences from children with nonautistic developmental disorders. Correlational analysis revealed that time spent listening to child-directed speech by children with ASD was related to their concurrent receptive language ability as well as to receptive language abilities 1 year later. This relationship did not hold for the other groups. Conclusion: The present study supports the hypothesis that children with ASD perform differently from typical peers in auditory preference paradigms and that performance in these tasks is related to concurrent and later language development.
Keywords: *Attention; *Autistic Disorder/px [Psychology]; *Child Behavior; *Choice Behavior; *Infant Behavior; *Speech Perception; Attention; Auditory comprehension; Autism spectrum disorders; Autistic Disorder; Child Behavior; Child, Preschool; Choice Behavior; Comprehension; Female; Humans; Infant; Infant Behavior; Language Development; Language comprehension; Male; Speech Perception; article; auditory stimulation; auditory system; autism; controlled study; correlation analysis; dept.cmd; developmental disorder; female; human; language; language ability; language development; major clinical study; male; peer group; preschool child; speech; time; toddler

Increasing stroke patients' success in self-medication programs using an interdisciplinary cognitive rehabilitation approach. - Purdy, Mary (Rehabilitation nursing : the official journal of the Association of Rehabilitation Nurses, 2007)
Rehabilitation programs strive to help patients become more independent in all aspects of daily living. Therefore, management of a patient's healthcare requirements should be an integral part of the rehabilitation program, including management of medications. Some rehabilitation programs implement self-medication programs (SMP); however, patients with cognitive deficits are often excluded. This study explored whether patients with cognitive deficits due to stroke could successfully complete an SMP using an interdisciplinary cognitive rehabilitation approach. Twenty-seven stroke patients and 36 debilitated patients with cognitive deficits participated in an SMP. A nurse and a pharmacist educated patients on their medications, and a speech-language pathologist provided cognitive rehabilitation to the stroke patients, which incorporated information from the SMP. Eighty-one percent of the stroke patients successfully completed the SMP, compared to 36% of the debilitated patients. Thus, an interdisciplinary approach to medication management for cognitively impaired stroke patients holds promise.
Keywords: *Cognition Disorders/rh [Rehabilitation]; *Patient Care Team/og [Organization & Administration]; *Patient Education as Topic/og [Organization & Administration]; *Self Administration; *Stroke/co [Complications]; Aged; Analysis of Variance; Case-Control Studies; Cerebrovascular Accident; Cognition Disorders; Cognition Disorders/et [Etiology]; Cognition Disorders/px [Psychology]; Curriculum; Humans; Length of Stay; Length of Stay/sn [Statistics & Numerical Data]; MLCS; MLOWN; Middle Aged; Needs Assessment; Nursing Assessment; Nursing Evaluation Research; Patient Care Team; Patient Education; Pharmacy Service, Hospital; Pharmacy Service, Hospital/og [Organization & Administration]; Problem Solving; Program Evaluation; Rehabilitation Nursing; Rehabilitation Nursing/og [Organization & Administration]; Self Administration; Self Administration/mt [Methods]; Self Administration/px [Psychology]; Severity of Illness Index; Speech-Language Pathology; Speech-Language Pathology/og [Organization & Administration]; Treatment Outcome; aged; analysis of variance; article; case control study; cerebrovascular accident; cognitive defect; curriculum; dept.cmd; drug self administration; evaluation; health care quality; hospital pharmacy; hospitalization; human; length of stay; methodology; middle aged; needs assessment; nursing assessment; nursing evaluation research; organization and management; patient care; patient education; problem solving; psychological aspect; rehabilitation nursing; speech disorder; statistics; treatment outcome

Ratings of communication competence by siblings of persons with Down syndrome - Smith, Sarah E.; Cascella, Paul W. (Education and Training in Developmental Disabilities, 2007)
This study surveyed 25 siblings of persons with Down Syndrome to gain an ecological perspective about important communication competence indicators. Siblings favorably described persons with Down Syndrome as “effective” and “good” communicators who “communicate to potential. “ Siblings regarded social communication skills as especially important, i.e., being able to communicate without fear, being able to express wants, needs, opinions, and feelings, being able to ask questions, and alerting partners to communication breakdowns. Siblings also regarded language comprehension as an important skill. Favorable descriptive labels were often applied to adult-aged persons with mild ID and normal hearing. Clinical implications are discussed focused on functional communication planning and implementation that takes into account the perspectives of family members, teachers, and rehabilitation personnel.
Keywords: dept.cmd; ⛔ No DOI found

Autism spectrum disorder in the second year: stability and change in syndrome expression - Chawarska, Katarzyna; Klin, Ami; Paul, Rhea; Volkmar, Fred (Journal of Child Psychology and Psychiatry, 2007)
Objectives: Increasing numbers of young children referred for a differential diagnosis of autism spectrum disorders (ASD) necessitates better understanding of the early syndrome expression and the utility of the existing state-of-the art diagnostic methods in this population. Method: Out of 31 infants under the age of 2 years referred for a differential diagnosis, 19 were diagnosed with autism, and 9 with pervasive developmental disorder-not otherwise specified (PDD- NOS) when reassessed at 3 years. We examined 1) the symptoms of ASD in the second year and changes in the syndrome expression by the age of three; 2) relationship between expert-assigned clinical diagnosis and diagnostic classification based on Autism Diagnostic Observation Schedule-Generic (ADOS-G) and Autism Diagnostic Interview-Revised (ADI-R) in the second year; 3) the relationship between direct observation and parental report of ASD symptoms. Results: Symptoms of autism and PDD- NOS in the second year were pronounced and stability of the clinical diagnosis was high. The agreement between clinician-assigned autism but not PDD- NOS diagnosis and the ADOS-G was high. However, sensitivity of the ADI-R diagnostic classification of autism was poor. Comparison of concurrent parental report and direct observation revealed discrepancies in severity ratings of key dyadic social behaviors. Changes in communication reflected acquisition of language accompanied by the emergence of unusual language characteristics. Symptoms of social dysfunction were relatively stable over time, and so was the severity of stereotyped behaviors. Conclusions: The study provides support for stability of clinical diagnosis and syndrome expression in the second year and highlights advantages and limitations of the ADI-R and ADOS-G for diagnosing and documenting symptoms of ASD in infants.
Keywords: ADI-R; ADOS-G; ASD; Assessment; Autism; Autistic Disorder; Child, Preschool; Communication; Diagnosis, Differential; Disease Progression; Early Diagnosis; Earlydiagnosis; Female; Humans; Infant; Infants; Interpersonal Relations; Language Development Disorders; Longitudinal studies; Male; PDD-NOS; Questionnaires; Social Behavior; Stereotyped Behavior; Toddlers; article; assessment; autism; communication disorder; controlled study; dept.cmd; differential diagnosis; disease severity; early diagnosis; female; follow up; human; infants; language disability; longitudinal studies; longitudinal study; male; observational study; patient referral; pervasive developmental disorder not otherwise specified; play; preschool child; psychologic assessment; psychological rating scale; sensitivity analysis; social behavior; social disability; social interaction; stereotypy; symptomatology; toddlers

Parental recognition of developmental problems in toddlers with autism spectrum disorders - Chawarska, Katarzyna; Paul, Rhea; Klin, Ami; Hannigen, Sarah; Dichtel, Laura E.; Volkmar, Fred (Journal of Autism and Developmental Disorders, 2007)
Symptoms of Autism Spectrum Disorders (ASD) begin to manifest during the first 2 years; there is limited evidence regarding type and timing of symptom onset. We examined factors related to parental age of recognition (AOR) of early abnormalities and the association between AOR and diagnosis and levels of functioning at 2 and 4 years in 75 toddlers with ASD. Results suggest significant differences between autism and PDD-NOS in the AOR and type of first concerns. Early social and motor delays as well as maternal age was associated with AOR. Later AOR was associated with poorer social-communicative and nonverbal cognitive functioning at 2 and 4. The findings are discussed in a context of identifying distinct developmental trajectories within the autism spectrum.
Keywords: Age Factors; Age of recognition; Autism; Autistic Disorder; Child, Preschool; Cognition Disorders; Developmental Disabilities; Early Diagnosis; Female; Follow-Up Studies; Humans; Infants; Male; Mass Screening; PDD-NOS; Parents; Recognition (Psychology); Regression; Severity of Illness Index; Social Behavior; article; autism; clinical feature; dept.cmd; developmental disorder; early diagnosis; functional assessment; human; major clinical study; maternal age; motor performance; nonverbal communication; parental attitude; peer-reviewed; preschool child; priority journal; social interaction

Focused stimulation for a child with autism spectrum disorder: A treatment study - Grela, Bernard G.; McLaughlin, Kathryn S. (Journal of Autism and Developmental Disorders, 2006)
This study explored the use of focused stimulation as an intervention technique for a three-year-old boy diagnosed with autism spectrum disorder (ASD). His parents were trained to use focused stimulation to facilitate comprehension of what is x doing question forms. Responses to question probes were collected at both pre- and post-treatment intervals. At the beginning of the study, the child did not respond correctly to any of the target questions. Following intervention, the child made significant gains towards the target goal, but little change towards a control goal used for comparison. These findings provide preliminary support for the usefulness of focused stimulation as an intervention strategy for at least some children with ASD.
Keywords: Attention; Autism spectrum disorder; Autistic Disorder; Child, Preschool; Comprehension; Early Intervention (Education); Focused stimulation; Follow-Up Studies; Generalization (Psychology); Humans; Imagination; Imitative Behavior; Language Development Disorders; Language Therapy; Male; Natural language procedures; Parent intervention; Play and Playthings; Speech Perception; article; autism; brain function; case report; child parent relation; cognitive therapy; comprehension; dept.cmd; focused stimulation; human; information processing; language; language development; male; peer-reviewed; preschool child; priority journal; questionnaire; statistical significance

Prediction of strategy usage by adults with aphasia - Purdy, Mary; Koch, Amy (Aphasiology, 2006)
Background: Management of aphasia often focuses on training augmentative communication strategies such as communication books, computerised systems, gestures, writing, or drawing. Although many individuals are able to acquire a targeted skill in a structured format, many do not successfully use the trained skill in more functional situations. Training alternative communication strategies can be a time-consuming project; thus, it would be beneficial if speech-language pathologists could predict, a priori, how a patient may respond to this type of treatment approach. It has been hypothesised that use of augmentative communication strategies requires executive functioning, specifically cognitive flexibility, which may be impaired following brain damage. Therefore, assessment of cognitive flexibility may help clinicians determine which persons with aphasia would most likely benefit from training of augmentative communication strategies. Aims: The purpose of this study was to develop a measure of cognitive flexibility and to determine whether this measure predicted strategy usage during a functional communication task. Methods and Procedures: A novel scoring system for the Communicative Abilities in Daily Living (CADL) was developed to capture the degree of participants' cognitive flexibility. This score was correlated with the Wisconsin Card Sorting Test (WCST), to determine the validity of the scoring system. The CADL cognitive flexibility score was then correlated with performance on a referential communication task. A multiple regression analysis was conducted with severity of aphasia as an additional predictor variable. Outcomes and Results: There was a significant correlation between the cognitive flexibility score from the CADL and the WCST, confirming the validity of the scoring system as a measure of cognitive flexibility. Results of the regression analysis demonstrated a significant relationship between the cognitive flexibility score and strategy usage on a functional communication task. This relationship remained significant when the overall severity of aphasia was added to the regression analysis, suggesting that cognitive flexibility is a stronger predictor of strategy usage than severity of aphasia. These results may provide clinicians insight into which individuals would benefit most from the training of compensatory strategies, leading to the development of more appropriate goals and treatment methods.
Keywords: adult; aged; aphasia; apraxia; article; clinical article; cognition; comorbidity; computer assisted tomography; control strategy; coping behavior; dept.cmd; disease association; disease severity; drawing; facilitated communication; fluency disorder; gesture; human; peer-reviewed; prediction; verbal communication; writing

Standardised speech-language tests and students with intellectual disability: a review of normative data. - Cascella, Paul W (Journal of intellectual & developmental disability, 2006)
Background: Before a school speech-language pathologist (SLP) utilises a standardised speech-language test with a student with intellectual disability (ID), the clinician should carefully consider the purpose of the test and whether the test includes students with ID in the normative group. Method: This project reviewed 49 tests published between 1994 and 2004 and their applicability to students with ID. Results: Students with mild ID were included in the norm group for 23 of the tests, but no tests included students with more significant ID. Separate norms for students with mild ID were included in 15 tests, but none met Salvia & Ysseldyke's (1995) suggested requirement that at least 100 students be included to represent a specific subgroup. A majority of the tests assessed receptive and expressive vocabulary, syntax, and grammar but no recent test measured a student's pragmatic communication. Conclusions: Clinicians are encouraged to supplement standardised tests with non-standardised procedures to document students' pragmatic, social, and functional communication abilities. © 2006 Australasian Society for the Study of Intellectual Disability Inc.
Keywords: *Intellectual Disability; *Language Disorders/di [Diagnosis]; *Language Disorders/ep [Epidemiology]; *Language Tests; *Speech Disorders/di [Diagnosis]; *Speech Disorders/ep [Epidemiology]; Humans; Intellectual disability; Language Disorders; Language Tests; Language test; Mental Retardation; Reference Values; Severity of Illness Index; Speech Disorders; Speech test; Student; adolescent; article; child; dept.cmd; diagnostic value; grammar; human; interpersonal communication; linguistics; major clinical study; mental deficiency; social adaptation; social aspect; social status; speech analysis; speech language pathologist; student; systematic review

An electrophysiologic approach to APD - Jirsa, Robert E; Musiek, Frank E (The Hearing journal, 2006)
Keywords: audiology; auditory cortex; auditory discrimination; auditory processing disorder; auditory stimulation; auditory threshold; dept.cmd; electrophysiology; evaluation; hearing acuity; human; hypoacusis; language; neurophysiology; short survey; speech perception; temporal lobe; voice onset time

Out of the mouths of babes: vocal production in infant siblings of children with ASD - Paul, Rhea; Fuerst, Yael; Ramsay, Gordon J.; Chawarska, Kasia; Klin, Ami (Journal of Child Psychology and Psychiatry, 2010)
Background: Younger siblings of children with autism spectrum disorders (ASD) are at higher risk for acquiring these disorders than the general population. Language development is usually delayed in children with ASD. The present study examines the development of pre-speech vocal behavior in infants at risk for ASD due to the presence of an older sibling with the disorder. Methods: Infants at high risk (HR) for ASD and those at low risk, without a diagnosed sibling (LR), were seen at 6, 9, and 12 months as part of a larger prospective study of risk for ASD in infant siblings. Standard clinical assessments were administered, and vocalization samples were collected during play with mother and a standard set of toys. Infant vocal behavior was recorded and analyzed for consonant inventory, presence of canonical syllables, and of non-speech vocalizations, in a cross-sectional design. Children were seen again at 24 months for provisional diagnosis. Results: Differences were seen between risk groups for certain vocal behaviors. Differences in vocal production in the first year of life were associated with outcomes in terms of autistic symptomotology in the second year. Conclusions: Early vocal behavior is a sensitive indicator of heightened risk for autistic symptoms in infants with a family history of ASD.
Keywords: *Child Development Disorders, Pervasive/px [Psychology]; *Infant Behavior/px [Psychology]; *Language Development; *Siblings/px [Psychology]; *Speech; Autism; Child Development Disorders, Pervasive; Child Development Disorders, Pervasive/ge [Genetics]; Child, Preschool; Cross-Sectional Studies; Female; Humans; Infant; Infant Behavior; Language Development; Male; Prospective Studies; Risk Factors; Siblings; Speech; Speech Acoustics; Speech Production Measurement; article; autism; child behavior; cross-sectional study; dept.cmd; female; genetics; human; infant; infant siblings; language development; male; preschool child; prospective study; psychological aspect; risk factor; sibling; speech; speech analysis; vocalization

Aphasia, alexia, and agraphia - Purdy, Mary (Reference Module in Neuroscience and Biobehavioral Psychology Encyclopedia of Mental Health (Second Edition), 2016)
Aphasia is a general language disorder resulting from brain damage, and alexia and agraphia are specific impairments in reading and writing, respectively. This article describes the symptoms associated with each disorder, the subtypes of each impairment, and the common causes. Assessment and management approaches consistent with the World Health Organization International Classification of Functioning (WHO-ICF) are briefly reviewed. © 2016 Elsevier Inc. All rights reserved.
Keywords: Acquired language disorders; Agraphia; Alexia; Aphasia; Assessment; Communication disorder; Dysgraphia; Dyslexia; Dysphasia; Management; WHO-ICF; dept.cmd

Intensive multimodal communication treatment for people with chronic aphasia - Purdy, Mary; Wallace, Sarah E. (Aphasiology, 2016)
Background: Clinicians often teach persons with aphasia (PWA) non-verbal strategies to compensate for reduced verbal communication. The manner in which they teach the strategies may have an impact on how well PWA generalise and use the strategies. Previously, multimodal communication treatment (MCT) taught multiple modalities simultaneously. While participants demonstrated some increase in the flexible use of strategies, many communication breakdowns continued to occur. Recent research suggests that intensive treatment protocols result in the greatest increase in skills.Aims: The purpose of this study was to determine whether intensive (2-3hours/day, 5 days/week, for 2 weeks) multimodality communication training for aphasia resulted in increased successful use of verbal and non-verbal communication modalities as well as increased successful communicative repairs during structured communication tasks.Methods & Procedures: Three participants with chronic aphasia completed four baseline sessions, 10 treatment sessions across two phases (i.e., five sessions per phase), and three post-treatment sessions.Outcomes & Results: Two of the three participants demonstrated gains in the acquisition of non-verbal strategies during training and increased use of strategies on a referential communication task.Conclusions: Although MCT delivered intensely resulted in increased use of non-verbal modalities for two out of three participants, the results were similar to that achieved through the use of a non-intensive treatment protocol. Therefore, future research is needed to examine other potential modifications to maximise the gains people with aphasia receive from multimodal interventions.
Keywords: Article; Cognitive Linguistic Quick Test; accuracy; adult; aphasia; case report; cognitive function test; communication; dept.cmd; disease severity; hemiparesis; human; intensive treatment; interrater reliability; male; middle aged; multimodality communication training; nonverbal communication; outcome assessment; peer-reviewed; physiotherapy; strategy usage; training

Perception of speech sounds in school-aged children with speech sound disorders - Preston, Jonathan L.; Irwin, Julia R.; Turcios, Jacqueline (Seminars in Speech and Language, 2015)
Children with speech sound disorders may perceive speech differently than children with typical speech development. The nature of these speech differences is reviewed with an emphasis on assessing phoneme-specific perception for speech sounds that are produced in error. Category goodness judgment, or the ability to judge accurate and inaccurate tokens of speech sounds, plays an important role in phonological development. The software Speech Assessment and Interactive Learning System, which has been effectively used to assess preschoolers' ability to perform goodness judgments, is explored for school-aged children with residual speech errors (RSEs). However, data suggest that this particular, task may not be sensitive to perceptual differences in school-aged children. The need for the development of clinical tools for assessment of speech perception in school-aged children with RSE is highlighted, and clinical suggestions are provided.
Keywords: Child; Female; Humans; Male; Phonetics; Speech; Speech Perception; Speech Sound Disorder; Speech sound disorder; assessment; child; dept.cmd; dept.psy; female; human; male; pathophysiology; phonetics; speech; speech perception; speech sound disorder

Ways of examining speech acts in young african american children: considering inside-out and outside-in approaches. - Dejarnette, Glenda; Rivers, Kenyatta O; Hyter, Yvette D (Topics in Language Disorders, 2015)
To develop a framework for further study of pragmatic behavior in young children from African American English (AAE) speaking backgrounds, one aspect of pragmatic behavior is explored in this article, specifically, speech acts. The aims of this article are to (1) examine examples of how external taxonomies (i.e., an “etic” or “outside-in” approach) have been applied to the speech act behavior of AAE child speakers and to note that etic approaches alone do not identify cultural characteristics that influence the presentation of speech acts in this population; (2) conceptualize a culture-sensitive framework where components of AAE speech act behaviors can be identified as gleaned from existing linguistic research; and (3) explain the utility of analyses of speech act behavior using taxonomies that have emerged from the cultural language style of AAE speakers, that is, an “emic” or “inside-out” approach.
Keywords: English speakers; communicative functions; dept.cmd; language behavior; pragmatic behavior; speech acts; young African American

Pragmatic language of african american children and adolescents: A systematic synthesis of the literature. - Hyter, Yvette D; Rivers, Kenyatta O; Dejarnette, Glenda (Topics in Language Disorders, 2015)
Purpose: A systematic review and synthesis was performed on published articles and dissertations produced between 1970 and 2013 that focused on selected pragmatic language behaviors of African American children and adolescents. Methods: Electronic databases and hand searches of articles located in the databases were used to identify the published articles and dissertations. Each article or dissertation was reviewed by at least 2 of the authors to determine whether it met the criteria for inclusion in this study. Selected observations of the documents that met criteria for inclusion were recorded on the Primary Research Appraisal Tool (PRAT; DeJarnette, Hyter, & Rivers, 2012), a data gathering and analysis framework developed by the authors specifically for this systematic synthesis. Results: The literature search resulted in 92 research articles and dissertations, 37 of which were eliminated because they did not meet all of the inclusion criteria. The documents that met our inclusion criteria focused primarily on the structure and/or content of narrative discourse rather than speech acts, other forms of discourse (e.g., conversation, expository), and presupposition/perspective taking skills. Six major themes identified in the major findings are used to summarize studies reviewed for this systematic synthesis. Conclusions: We (a) explain the current state of knowledge about African American pragmatic language behaviors, (b) explain major findings and implications of the extant literature in this topical area and how it may inform speech-language pathology practice, and (c) identify directions for future research on pragmatic language of African American children and adolescents.
Keywords: African American; communication functions; dept.cmd; discourse; pragmatic language; presupposition; speech acts; systematic review and synthesis; theory of mind

Phonological complexity in school-aged children who stutter and exhibit a language disorder. - Wolk, Lesley; LaSalle, Lisa R (Journal of fluency disorders, 2015)
PURPOSE: The Index of Phonological Complexity and the Word Complexity Measure are two measures of the phonological complexity of a word. Other phonological measures such as phonological neighborhood density have been used to compare stuttered versus fluent words. It appears that in preschoolers who stutter, the length and complexity of the utterance is more influential than the phonetic features of the stuttered word. The present hypothesis was that in school-age children who stutter, stuttered words would be more phonologically complex than fluent words, when the length and complexity of the utterance containing them is comparable. School-age speakers who stutter were hypothesized to differ from those with a concomitant language disorder., METHODS: Sixteen speakers, six females and ten males (M age=12;3; Range=7;7 to 19;5) available from an online database, were divided into eight who had a concomitant language disorder (S+LD) and eight age- and sex-matched speakers who did not (S-Only)., RESULTS: When all stuttered content words were identified, S+LD speakers produced more repetitions, and S-Only speakers produced more inaudible sound prolongations. When stuttered content words were matched to fluent content words and when talker groups were combined, stuttered words were significantly (p<=0.01) higher in both the Index of Phonological Complexity and the Word Complexity Measure and lower in density ("sparser") than fluent words., CONCLUSIONS: Results corroborate those of previous researchers. Future research directions are suggested, such as cross-sectional designs to evaluate developmental patterns of phonological complexity and stuttering plus language disordered connections., EDUCATIONAL OBJECTIVES: The reader will be able to: (a) Define and describe phonological complexity; (b) Define phonological neighborhood density and summarize the literature on the topic; (c) Describe the Index of Phonological Complexity (IPC) for a given word; (d) Describe the Word Complexity Measure (WCM) for a given word; (e) Summarize two findings from the current study and describe how each relates to studies of phonological complexity and fluency disorders. Copyright © 2014 Elsevier Inc. All rights reserved.
Keywords: *Language; *Linguistics; *Phonetics; *Stuttering; Adolescent; Adult; Article; Child; Concomitant disorders; Female; Humans; Language; Language disorders; Linguistics; Male; Phonetics; Phonological complexity; Schools; Speech; Speech Production Measurement; Stuttering; adolescent; adult; child; controlled study; data base; dept.cmd; female; fluency disorder; human; language; language disability; linguistics; male; phoneme; phonetics; school; school child; speech; speech analysis; stuttering

Development of an audiovisual speech perception app for children with autism spectrum disorders - Irwin, Julia; Preston, Jonathan; Brancazio, Lawrence; D'Angelo, Michael; Turcios, Jacqueline (Clinical Linguistics & Phonetics, 2015)
Perception of spoken language requires attention to acoustic as well as visible phonetic information. This article reviews the known differences in audiovisual speech perception in children with autism spectrum disorders (ASD) and specifies the need for interventions that address this construct. Elements of an audiovisual training program are described. This researcher-developed program delivered via an iPad app presents natural speech in the context of increasing noise, but supported with a speaking face. Children are cued to attend to visible articulatory information to assist in perception of the spoken words. Data from four children with ASD ages 8-10 are presented showing that the children improved their performance on an untrained auditory speech-in-noise task.
Keywords: Attention; Audiovisual Aids; Audiovisual app; Autism spectrum disorder; Child; Child Development Disorders, Pervasive; Comprehension; Humans; Lipreading; Male; Mobile Applications; Pattern Recognition, Visual; Phonetics; Semantics; Speech Perception; Speech perception; attention; audiovisual aid; child; comprehension; dept.cmd; dept.hls; dept.psy; human; lip reading; male; mobile application; pattern recognition; phonetics; psychology; semantics; speech perception

Ultrasound visual feedback treatment and practice variability for residual speech sound errors - Preston, Jonathan L.; McCabe, Patricia; Rivera-Campos, Ahmed; Whittle, Jessica L.; Landry, Erik; Maas, Edwin (Journal of Speech Language and Hearing Research, 2014)
Purpose: The goals were to (a) test the efficacy of a motor-learning-based treatment that includes ultrasound visual feedback for individuals with residual speech sound errors and (b) explore whether the addition of prosodic cueing facilitates speech sound learning. Method: A multiple-baseline, single-subject design was used, replicated across 8 participants. For each participant, 1 sound context was treated with ultrasound plus prosodic cueing for 7 sessions, and another sound context was treated with ultrasound but without prosodic cueing for 7 sessions. Sessions included ultrasound visual feedback as well as non-ultrasound treatment. Word-level probes assessing untreated words were used to evaluate retention and generalization. Results: For most participants, increases in accuracy of target sound contexts at the word level were observed with the treatment program regardless of whether prosodic cueing was included. Generalization between onset singletons and clusters was observed, as was generalization to sentence-level accuracy. There was evidence of retention during posttreatment probes, including at a 2-month follow-up. Conclusion: A motor-based treatment program that includes ultrasound visual feedback can facilitate learning of speech sounds in individuals with residual speech sound errors.
Keywords: Child; Cues; Feedback, Sensory; Female; Humans; Male; Phonetics; Speech; Speech Sound Disorder; Speech Therapy; Ultrasonography; Young Adult; association; child; dept.cmd; diagnostic imaging; echography; female; human; male; pathophysiology; phonetics; physiology; procedures; sensory feedback; speech; speech sound disorder; speech therapy; young adult; ⚠️ Invalid DOI

Glutamate and choline levels predict individual differences in reading ability in emergent readers - Pugh, Kenneth R.; Frost, Stephen J.; Rothman, Douglas L.; Hoeft, Fumiko; Tufo, Stephanie N. Del; Mason, Graeme F.; Molfese, Peter J.; Mencl, W. Einar; Grigorenko, Elena L.; Landi, Nicole; Preston, Jonathan L.; Jacobsen, Leslie; et al. (The Journal of Neuroscience, 2014)
Reading disability is a brain-based difficulty in acquiring fluent reading skills that affects significant numbers of children. Although neuroanatomical and neurofunctional networks involved in typical and atypical reading are increasingly well characterized, the underlying neurochemical bases of individual differences in reading development are virtually unknown. The current study is the first to examine neurochemistry in children during the critical period in which the neurocircuits that support skilled reading are still developing. In a longitudinal pediatric sample of emergent readers whose reading indicators range on a continuum from impaired to superior, we examined the relationship between individual differences in reading and reading-related skills and concentrations of neurometabolites measured using magnetic resonance spectroscopy. Both continuous and group analyses revealed that choline and glutamate concentrations were negatively correlated with reading and related linguistic measures in phonology and vocabulary (such that higher concentrations were associated with poorer performance). Correlations with behavioral scores obtained 24 months later reveal stability for the relationship between glutamate and reading performance. Implications for neurodevelopmental models of reading and reading disability are discussed, including possible links of choline and glutamate to white matter anomalies and hyperexcitability. These findings point to new directions for research on gene-brain-behavior pathways in human studies of reading disability. © 2014 the authors.
Keywords: 4 aminobutyric acid; Aspartic Acid; Brain; Child; Choline; Decoding; Dyslexia; Female; Glutamic Acid; Humans; Individual differences; Individuality; Learning; MRS; Magnetic Resonance Spectroscopy; Male; Phonetics; Phonological processing; Predictive Value of Tests; Reading; Reading disability; Vocabulary; article; behavior; child; choline; decoding; dept.cmd; female; gamma-Aminobutyric Acid; glutamic acid; human; human experiment; individual differences; language ability; linguistics; male; nerve cell differentiation; nerve excitability; normal human; nuclear magnetic resonance spectroscopy; phonetics; phonological processing; priority journal; reading; reading disability; school child; speech

Structural brain differences in school-age children with residual speech sound errors. - Preston, Jonathan L; Molfese, Peter J; Mencl, W Einar; Frost, Stephen J; Hoeft, Fumiko; Fulbright, Robert K; Landi, Nicole; Grigorenko, Elena L; Seki, Ayumi; Felsenfeld, Susan; Pugh, Kenneth R (Brain and Language, 2014)
The purpose of the study was to identify structural brain differences in school-age children with residual speech sound errors. Voxel based morphometry was used to compare gray and white matter volumes for 23 children with speech sound errors, ages 8;6-11;11, and 54 typically speaking children matched on age, oral language, and IQ. We hypothesized that regions associated with production and perception of speech sounds would differ between groups. Results indicated greater gray matter volumes for the speech sound error group relative to typically speaking controls in bilateral superior temporal gyrus. There was greater white matter volume in the corpus callosum for the speech sound error group, but less white matter volume in right lateral occipital gyrus. Results may indicate delays in neuronal pruning in critical speech regions or differences in the development of networks for speech perception and production. Copyright © 2013 Elsevier Inc. All rights reserved.
Keywords: *Brain/pa [Pathology]; *Language Development Disorders/pa [Pathology]; *Phonetics; *Speech Perception; Brain; Child; Children; Humans; Language Development Disorders; Magnetic Resonance Imaging; Phonetics; Speech Perception; Speech sound disorders; Speech sound errors; Structural MRI; article; brain region; brain size; child; clinical article; controlled study; corpus callosum; dept.cmd; female; gray matter; human; male; neuroanatomy; occipital gyrus; school child; speech articulation; speech perception; speech sound disorder; speech sound error; superior temporal gyrus; voxel based morphometry; white matter

Neurophysiology of speech differences in childhood apraxia of speech - Preston, Jonathan L; Molfese, Peter J; Gumkowski, Nina; Sorcinelli, Andrea; Harwood, Vanessa; Irwin, Julia; Landi, Nicole (Developmental Neuropsychology, 2014)
Event-related potentials (ERPs) were recorded during a picture naming task of simple and complex words in children with typical speech and with childhood apraxia of speech (CAS). Results reveal reduced amplitude prior to speaking complex (multisyllabic) words relative to simple (monosyllabic) words for the CAS group over the right hemisphere during a time window thought to reflect phonological encoding of word forms. Group differences were also observed prior to production of spoken tokens regardless of word complexity during a time window just prior to speech onset (thought to reflect motor planning/programming). Results suggest differences in pre-speech neurolinguistic processes.
Keywords: Adolescent; Apraxias; Child; Evoked Potentials; Female; Humans; Linguistics; Male; Neurophysiology; Speech; adolescent; apraxia; article; child; comparative study; dept.cmd; dept.psy; evoked response; female; human; linguistics; male; neurophysiology; pathophysiology; physiology; speech

A multimodal communication program for aphasia during inpatient rehabilitation: A case study. - Wallace, Sarah E; Purdy, Mary; Skidmore, Elizabeth (NeuroRehabilitation, 2014)
BACKGROUND: Communication is essential for successful rehabilitation, yet few aphasia treatments have been investigated during the acute stroke phase. Alternative modality use including gesturing, writing, or drawing has been shown to increase communicative effectiveness in people with chronic aphasia. Instruction in alternative modality use during acute stroke may increase patient communication and participation, therefore resulting in fewer adverse situations and improved rehabilitation outcomes., OBJECTIVE: The study purpose was to explore a multimodal communication program for aphasia (MCPA) implemented during acute stroke rehabilitation. MCPA aims to improve communication modality production, and to facilitate switching among modalities to resolve communication breakdowns., METHODS: Two adults with severe aphasia completed MCPA beginning at 2 and 3 weeks post onset a single left-hemisphere stroke. Probes completed during each session allowed for evaluation of modality production and modality switching accuracy., RESULTS: Participants completed MCPA (10 and 14 treatment sessions respectively) and their performance on probes suggested increased accuracy in the production of various alternate communication modalities. However, increased switching to an alternate modality was noted for only one participant., CONCLUSIONS: Further investigation of multimodal treatment during inpatient rehabilitation is warranted. In particular, comparisons between multimodal and standard treatments would help determine appropriate interventions for this setting.
Keywords: *Aphasia/px [Psychology]; *Aphasia/rh [Rehabilitation]; *Communication; *Communication Aids for Disabled; *Communication Disorders/px [Psychology]; *Communication Disorders/rh [Rehabilitation]; Aphasia; Article; Communication; Communication Aids for Disabled; Communication Disorders; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Psychomotor Performance; Stroke; Stroke Rehabilitation; Stroke/co [Complications]; Stroke/px [Psychology]; Treatment Outcome; acute rehabilitation; adult; aphasia; case report; cerebrovascular accident; communication aid; complication; dept.cmd; female; hospital patient; human; interpersonal communication; left hemisphere; male; mental performance; middle aged; multimodal treatment; neuropsychological test; psychological rating scale; psychology; psychomotor performance; rehabilitation care; stroke; treatment outcome

Ultrasound biofeedback treatment for persisting childhood apraxia of speech - Preston, Jonathan L.; Brick, Nickole; Landi, Nicole (American Journal of Speech-language Pathology, 2013)
Purpose: The purpose of this study was to evaluate the efficacy of a treatment program that includes ultrasound biofeedback for children with persisting speech sound errors associated with childhood apraxia of speech (CAS). Method: Six children ages 9-15 years participated in a multiple baseline experiment for 18 treatment sessions during which treatment focused on producing sequences involving lingual sounds. Children were cued to modify their tongue movements using visual feedback from real-time ultrasound images. Probe data were collected before, during, and after treatment to assess word-level accuracy for treated and untreated sound sequences. As participants reached preestablished performance criteria, new sequences were introduced into treatment. Results: All participants met the performance criterion (80% accuracy for 2 consecutive sessions) on at least 2 treated sound sequences. Across the 6 participants, performance criterion was met for 23 of 31 treated sequences in an average of 5 sessions. Some participants showed no improvement in untreated sequences, whereas others showed generalization to untreated sequences that were phonetically similar to the treated sequences. Most gains were maintained 2 months after the end of treatment. The percentage of phonemes correct increased significantly from pretreatment to the 2-month follow-up. Conclusion: A treatment program including ultrasound biofeedback is a viable option for improving speech sound accuracy in children with persisting speech sound errors associated with CAS.
Keywords: Adolescent; Apraxias; Articulation; Biofeedback, Psychology; Child; Childhood apraxia of speech; Children; Cues; Efficacy; Feedback, Sensory; Follow-Up Studies; Humans; Intervention; Male; Phonetics; Speech; Speech Disorders; Speech Therapy; Speech sound disorders; Tongue; Treatment Outcome; Ultrasonic Therapy; adolescent; apraxia; article; articulation; association; child; childhood apraxia of speech; children; clinical trial; dept.cmd; echography; efficacy; follow up; human; intervention; male; methodology; pathophysiology; phonetics; physiology; psychophysiology; sensory feedback; speech; speech disorder; speech sound disorders; speech therapy; tongue; treatment outcome; ultrasound therapy

Toward improved spectral measures of /s/: results from adolescents - Koenig, Laura L.; Shadle, Christine H.; Preston, Jonathan L.; Mooshammer, Christine R. (Journal of Speech Language and Hearing Research, 2013)
Purpose: This article introduces theoretically driven acoustic measures of /s/ that reflect aerodynamic and articulatory conditions. The measures were evaluated by assessing whether they revealed expected changes over time and labiality effects, along with possible gender differences suggested by past work. Method: Productions of /s/ were extracted from various speaking tasks from typically speaking adolescents (6 boys, 6 girls). Measures were made of relative spectral energies in low-(550-3000 Hz), mid-(3000-7000 Hz), and high-frequency regions (7000-11025 Hz); the mid-frequency amplitude peak; and temporal changes in these parameters. Spectral moments were also obtained to permit comparison with existing work. Results: Spectral balance measures in low-mid and mid-high frequency bands varied over the time course of /s/, capturing the development of sibilance at mid-fricative along with showing some effects of gender and labiality. The mid-frequency spectral peak was significantly higher in nonlabial contexts, and in girls. Temporal variation in the mid-frequency peak differentiated +/- labial contexts while normalizing over gender. Conclusions: The measures showed expected patterns, supporting their validity. Comparison of these data with studies of adults suggests some developmental patterns that call for further study. The measures may also serve to differentiate some cases of typical and misarticulated /s/.
Keywords: Acoustics; Adolescent; Adolescents; Development; Female; Humans; Lip; Male; Phonetics; Reference Values; Sex Characteristics; Speech; Speech Acoustics; Speech production; Verbal Behavior; acoustics; adolescent; adolescents; article; comparative study; dept.cmd; development; female; human; lip; male; phonetics; reference value; sexual development; speech; speech production; verbal behavior

Preschool speech error patterns predict articulation and phonological awareness outcomes in children with histories of speech sound disorders. - Preston, Jonathan L; Hull, Margaret; Edwards, Mary Louise (American journal of speech-language pathology, 2013)
Purpose: To determine if speech error patterns in preschoolers with speech sound disorders (SSDs) predict articulation and phonological awareness (PA) outcomes almost 4 years later. Method: Twenty-five children with histories of preschool SSDs (and normal receptive language) were tested at an average age of 4;6 (years;months) and were followed up at age 8;3. The frequency of occurrence of preschool distortion errors, typical substitution and syllable structure errors, and atypical substitution and syllable structure errors was used to predict later speech sound production, PA, and literacy outcomes. Results: Group averages revealed below-average schoolage articulation scores and low-average PA but ageappropriate reading and spelling. Preschool speech error patterns were related to school-age outcomes. Children for whom >10% of their speech sound errors were atypical had lower PA and literacy scores at school age than children who produced <10% atypical errors. Preschoolers who produced more distortion errors were likely to have lower school-age articulation scores than preschoolers who produced fewer distortion errors. Conclusion: Different preschool speech error patterns predict different school-age clinical outcomes. Many atypical speech sound errors in preschoolers may be indicative of weak phonological representations, leading to long-term PA weaknesses. Preschoolers' distortions may be resistant to change over time, leading to persisting speech sound production problems. © American Speech-Language-Hearing Association.
Keywords: *Articulation Disorders/di [Diagnosis]; *Language Tests; *Phonetics; *Speech; *Speech Articulation Tests; Awareness; Child; Child Language; Child, Preschool; Female; Follow-Up Studies; Humans; Language Disorders/di [Diagnosis]; Literacy; Male; Outcomes; Phonological awareness; Predictive Value of Tests; Psycholinguistics; Reading; Speech Production Measurement; Speech Sound Disorder; Speech production; Speech sound disorders; dept.cmd

The relationship between phonological and auditory processing and brain organization in beginning readers - Pugh, Kenneth R.; Landi, Nicole; Preston, Jonathan L.; Mencl, W. Einar; Austin, Alison C.; Sibley, Daragh; Fulbright, Robert K.; Seidenberg, Mark S.; Grigorenko, Elena L.; Constable, R. Todd; Molfese, Peter; Frost, Stephen J. (Brain and Language, 2013)
We employed brain-behavior analyses to explore the relationship between performance on tasks measuring phonological awareness, pseudoword decoding, and rapid auditory processing (all predictors of reading (dis)ability) and brain organization for print and speech in beginning readers. For print-related activation, we observed a shared set of skill-correlated regions, including left hemisphere temporoparietal and occipitotemporal sites, as well as inferior frontal, visual, visual attention, and subcortical components. For speech-related activation, shared variance among reading skill measures was most prominently correlated with activation in left hemisphere inferior frontal gyrus and precuneus. Implications for brain-based models of literacy acquisition are discussed. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Awareness; Brain; Brain Mapping; Child; Child, Preschool; Decoding; FMRI; Female; Humans; Individual differences; Male; Phonological awareness; Photic Stimulation; Psychomotor Performance; Rapid auditory processing; Reading; Speech; Speech Perception; Thalamus; Visual Perception; article; attention; child; dept.cmd; female; frontal lobe; hearing; human; human experiment; inferior frontal gyrus; left hemisphere; male; neurophysiology; normal human; occipital lobe; parietal lobe; phonetics; precuneus; preschool child; printing; reading; school child; speech; task performance; temporal lobe; visual cortex; word recognition

Auditory cortical processing in noise in younger and older adults - Mccullagh, Jennifer; Shinn, Jennifer B (Hearing, Balance and Communication, 2013)
Objective: A common clinical complaint among older adults is difficulty hearing in noise, even in those with normal or near-normal peripheral hearing sensitivity. Researchers have demonstrated behavioral hearing in noise deficits in older adults, but to date limited evidence, particularly objective, exists elucidating the effects of age on auditory cortical processing in noise. The purpose of this investigation was to explore age related differences in auditory cortical processing at multiple signal-to-noise ratios (SNRs). Study design: Twenty normal-hearing young adults and 15 normal-hearing older adults participated in the study. Late auditory evoked potential (N1 and P2) latencies and amplitudes were measured in quiet and at three signal-to-noise ratios (SNRs) (+ 20, + 10, and 0 SNR). Repeated measures analyses of variance (ANOVA) were utilized to determine if statistically significant differences existed. Results: Significant group by listening condition interactions existed for N1 and P2 amplitudes. P2 latencies were significantly longer for the older adult group compared to the younger adult group. In addition, N1 and P2 amplitudes were significantly smaller for the younger adult group compared to the older adult group. Conclusion: Results suggest a possibly greater reduction in the synchronous neuronal response from quiet to noisy conditions in older adults than in younger adults. © 2013 Informa Healthcare.
Keywords: Aging; Auditory late potentials; Hearing in noise; N1; P2; dept.cmd; peer-reviewed

Functional brain activation differences in school-age children with speech sound errors: speech and print processing - Preston, Jonathan L.; Felsenfeld, Susan; Frost, Stephen J.; Mencl, W. Einar; Fulbright, Robert K.; Grigorenko, Elena L.; Landi, Nicole; Seki, Ayumi; Pugh, Kenneth R. (Journal of Speech Language and Hearing Research, 2012)
Purpose: To examine neural response to spoken and printed language in children with speech sound errors (SSE). Method: Functional magnetic resonance imaging was used to compare processing of auditorily and visually presented words and pseudowords in 17 children with SSE, ages 8; 6[years; months] through 10; 10, with 17 matched controls. Results: When processing spoken words and pseudowords, the SSE group showed less activation than typically speaking controls in left middle temporal gyrus. They also showed greater activation than controls in several cortical and subcortical regions (e. g., left superior temporal gyrus, globus pallidus, insula, fusiform, and bilateral parietal regions). In response to printed words and pseudowords, children with SSE had greater activation than controls in regions including bilateral fusiform and anterior cingulate. Some differences were found in both speech and print processing that that may be associated with children with SSE failing to show common patterns of task-induced deactivation and/or attentional resource allocation. Conclusion: Compared with controls, children with SSE appear to rely more on several dorsal speech perception regions and less on ventral speech perception regions. When processing print, numerous regions were observed to be activated more for the SSE group than for controls.
Keywords: Brain; Cerebral Cortex; Child; Female; Functional magnetic resonance imaging (fMRI); Globus Pallidus; Gyrus Cinguli; Humans; Language Development Disorders; Magnetic Resonance Imaging; Male; Parietal Lobe; Phonetics; Photic Stimulation; Print processing; Reading; Speech; Speech Perception; Speech perception; Speech sound errors; Temporal Lobe; Visual Cortex; article; brain; brain cortex; child; cingulate gyrus; dept.cmd; female; globus pallidus; human; language disability; male; nuclear magnetic resonance imaging; parietal lobe; pathophysiology; phonetics; photostimulation; physiology; reading; speech; speech perception; temporal lobe; visual cortex

Auditory cortical processing in noise in normal-hearing young adults - Mccullagh, Jennifer; Musiek, Frank E; Shinn, Jennifer B (Audiological Medicine, 2012)
Objective: The ability to hear in background noise is related to the processing of the incoming acoustic signal in the peripheral auditory system as well as the central auditory nervous system (CANS). Electrophysiological tests have the ability to demonstrate the underlying neural integrity of the CANS, but to date a lack of literature exists demonstrating the effects of background noise on auditory cortical potentials. Therefore, the purpose of this investigation was to systematically investigate the effects of white noise on tone burst-evoked late auditory evoked potentials (N1, P2, and P3) in normal hearing young adults. Study Design: Twenty young-adult normal-hearing individuals served as subjects. A comparison of the late auditory evoked potentials (N1, P2, and P3) was made at multiple signal-to-noise ratios (SNRs) (quiet, + 20, + 10, 0). N1, P2, and P3 were elicited and both amplitude and latency were measured for each of the potentials. A standard oddball paradigm with binaural stimulation was used to evoke the potentials. Repeated Measures Analyses of Variance (ANOVA) were conducted for both the experimental factors of amplitude and latency with within subjects factors of condition (quiet, + 20, + 10, 0). Results: Results indicated no significant differences in N1, P2, or P3 amplitude or latency between the quiet and + 20 SNR condition; however, at poorer SNRs significant N1, P2, and P3 amplitude and/or latency differences were observed. Conclusion: The results indicate a change in higher-order neural function related to the presence of increased noise in the environment. © 2012 Informa Healthcare.
Keywords: Auditory evoked potentials; Central auditory processing; Hearing in noise; Late auditory evoked potentials; N1; P2; P3; Signal to noise ratio; adult; amplitude modulation; article; auditory nervous system; auditory stimulation; central nervous system; controlled study; dept.cmd; electrophysiology; evoked auditory response; female; hearing; human; human experiment; late auditory evoked potential; male; normal human; priority journal; sensory system electrophysiology; signal noise ratio

Searching for Potocki–Lupski syndrome phenotype: A patient with language impairment and no autism - Ercan-Sencicek, A. Gulhan; Wright, Nicole R. Davis; Frost, Stephen J.; Fulbright, Robert K.; Felsenfeld, Susan; Hart, Lesley; Landi, Nicole; Mencl, W. Einar; Sanders, Stephan J.; Pugh, Kenneth R.; State, Matthew W.; Grigorenko, Elena L. (Brain & Development, 2011)
Potocki-Lupski syndrome (PTLS; OMIM 610883) is a genomic syndrome that arises as a result of a duplication of 17p11.2. Although numerous cases of individuals with PTLS have been presented in the literature, its behavioral characterization is still ambiguous. We present a male child with a de novo dup(17)(p11.2p11.2) and he does not possess any autistic features, but is characterized by severe speech and language impairment. In the context of the analyses of this patient and other cases of PTLS, we argue that the central feature of the syndrome appears to be related to diminished speech and language capacity, rather than the specific social deficits central to autism. © 2011.
Keywords: 17p11.2; Autistic Disorder; Child; Chromosomes, Human, Pair 17; Humans; Inv(8)(q21.3-q24.1); Language Disorders; Language and speech impairment; Male; Phenotype; Potocki Lupski syndrome; Potocki-Lupski syndrome; Smith-Magenis Syndrome; academic achievement; adaptive behavior; article; case report; child; child development; chromosome 17p; chromosome duplication; clinical feature; dept.cmd; functional magnetic resonance imaging; genetic disorder; human; intelligence; language development; language disability; male; malformation syndrome; school child

Phonetic variability in residual speech sound disorders exploration of subtypes - Preston, Jonathan L.; Koenig, Laura L. (Topics in Language Disorders, 2011)
Purpose: To explore whether subgroups of children with residual speech sound disorders (R-SSDs) can be identified through multiple measures of token-to-token phonetic variability (changes in one spoken production to the next). Method: Children with R-SSDs were recorded during a rapid multisyllabic picture naming task and an oral diadochokinetic task. Transcription-based and acoustic measures of token-to-token variability were derived. Articulation accuracy and general indices of language skills were measured as well. Results: Low correlations were observed between transcription-based and acoustic measures of phonetic variability, and among the acoustic measures themselves. Children who were the most variable on one measure were not necessarily highly variable on other measures. Transcription-based measures of variability were associated with language skills. Conclusions: Measures of phonetic variability did not identify children in the sample as consistently high or low. Data do not support the notion that clear subgroups based on phonetic variability can be reliably identified in children with R-SSDs. The link between highly variable phonetic output (quantified by transcription-based measures) and lower language skills requires further exploration.
Keywords: acoustic analysis; dept.cmd; phonetic variability; residual speech sound disorders

Identifying residual speech sound disorders in bilingual children: A japanese-english case study - Preston, Jonathan L.; Seki, Ayumi (American Journal of Speech-language Pathology, 2011)
Purpose: To describe (a) the assessment of residual speech sound disorders (SSDs) in bilinguals by distinguishing speech patterns associated with second language acquisition from patterns associated with misarticulations and (b) how assessment of domains such as speech motor control and phonological awareness can provide a more complete understanding of SSDs in bilinguals. Method: A review of Japanese phonology is provided to offer a context for understanding the transfer of Japanese to English productions. A case study of an 11-year-old is presented, demonstrating parallel speech assessments in English and Japanese. Speech motor and phonological awareness tasks were conducted in both languages. Results: Several patterns were observed in the participant's English that could be plausibly explained by the influence of Japanese phonology. However, errors indicating a residual SSD were observed in both Japanese and English. A speech motor assessment suggested possible speech motor control problems, and phonological awareness was judged to be within the typical range of performance in both languages. Conclusion: Understanding the phonological characteristics of the native language can help clinicians recognize speech patterns in the second language associated with transfer. Once these differences are understood, patterns associated with a residual SSD can be identified. Supplementing a relational speech analysis with measures of speech motor control and phonological awareness can provide a more comprehensive understanding of a client's strengths and needs.
Keywords: Articulation; Assessment; Bilingualism; Residual speech sound disorders; Speech motor control; dept.cmd

Attentional regulation in young twins with probable stuttering, high nonfluency, and typical fluency. - Felsenfeld, Susan; van Beijsterveldt, Catharina Eugenie Maria; Boomsma, Dorret Irene (Journal of Speech, Language, and Hearing Research, 2010)
PURPOSE: Using a sample of 20,445 Dutch twins, this study examined the relationship between speech fluency and attentional regulation in children. A secondary objective was to identify etiological overlap between nonfluency and poor attention using fluency-discordant twin pairs., METHOD: Three fluency groups were created at age 5 using a parent questionnaire: (a) probable stuttering (PS; N=826; 4.0%), highly nonfluent (HNF; N=547; 2.7%), and typically fluent (TF; N=19,072; 93%). Multiple scales assessing attention, primarily self-regulation/inhibition, were obtained from both parents when children were ages 5 and 7 and from teachers when children were age 7., RESULTS: When compared with the TF controls, both the PS and HNF children received higher (i.e., more problematic) scores on parental attention ratings at both ages (p<.002). Effect sizes were moderate for both groups. Teacher and parent ratings were generally comparable. The discordant co-twin analyses suggested that nonfluency and attention were influenced by potentially overlapping genetic and shared environmental factors., CONCLUSIONS: The liability to express both high nonfluency and problems with self-regulation/inhibition may arise from a common set of pathogenic mechanisms. This supports emerging models of stuttering, which propose that poor fluency may be part of a broader network of impaired self-regulatory processes.
Keywords: *Attention Deficit Disorder with Hyperactivity/co [Complications]; *Attention/ph [Physiology]; *Executive Function/ph [Physiology]; *Speech/ph [Physiology]; *Stuttering/co [Complications]; Attention; Attention Deficit Disorder with Hyperactivity; Attention Deficit Disorder with Hyperactivity/px [Psychology]; Case-Control Studies; Child; Child, Preschool; Cohort Studies; Diseases in Twins; Executive Function; Female; Humans; Inhibition (Psychology); Inhibition, Psychological; Longitudinal Studies; Male; Nonfluency; Reference Values; Self Efficacy; Speech; Speech Production Measurement; Stuttering; Stuttering/pp [Physiopathology]; Stuttering/px [Psychology]; Twins; article; attention; attention deficit disorder; case control study; child; cohort analysis; comparative study; dept.cmd; executive function; female; human; inhibition (psychology); longitudinal study; male; pathophysiology; physiology; preschool child; psychological aspect; reference value; self concept; speech; speech analysis; stuttering; twins; ⚠️ Invalid DOI

Impact of chromosome 4p-Syndrome on communication and expressive language skills: A preliminary investigation - Marshall, Althea T (Language, speech, and hearing services in schools, 2010)
PURPOSE: The purpose of this investigation was to examine the impact of Chromosome 4p- syndrome on the communication and expressive language phenotype of a large cross-cultural population of children, adolescents, and adults., METHOD: A large-scale survey study was conducted and a descriptive research design was used to analyze quantitative and qualitative data regarding the communication and expressive language manifestations of 200 children, youth, and adults from 16 countries and Puerto Rico who had been diagnosed with 4p conditions, including Wolf-Hirschhorn syndrome (WHS), Pitt-Rogers-Danks syndrome (PRDS), Proximal 4p Deletion syndrome, and complex chromosomal rearrangements associated with 4p-., RESULTS: Individuals with Chromosome 4p- syndrome represent a heterogeneous population with complex phenotypic profiles. The majority of the participants exhibited communication and expressive language skills below the 36-month developmental functioning level. A relatively small cohort of the study population exhibited advanced expressive language skills, a finding not reported in the professional literature., CONCLUSION: Results broaden the spectrum of expressive language skills associated with Chromosome 4p- syndrome and highlight the communication potential of a subset of individuals with 4p abnormalities for development of advanced language structures. It is hypothesized that the largest 4p deletion, which includes the 4p16.3 band and contiguous gene regions, results in the most severely affected expressive language phenotype.
Keywords: *Chromosome Disorders/ge [Genetics]; *Chromosome Disorders/px [Psychology]; *Chromosomes, Human, Pair 4; *Communication; *Language; Adolescent; Adult; Child; Child, Preschool; Chromosome Disorders; Chromosome Disorders/co [Complications]; Chromosomes, Human, Pair 4; Cohort Studies; Communication; Communication Disorders; Communication Disorders/co [Complications]; Communication Disorders/ge [Genetics]; Cross-Cultural Comparison; Developmental disabilities; Female; Genetics; Humans; Infant; Language; Male; Middle Aged; Phenotype; Syndrome; Wolf Hirschhorn syndrome; Wolf-Hirschhorn Syndrome; Wolf-Hirschhorn Syndrome/co [Complications]; Wolf-Hirschhorn Syndrome/ge [Genetics]; Wolf-Hirschhorn Syndrome/px [Psychology]; Young Adult; adolescent; adult; article; child; chromosome 4; chromosome disorder; cohort analysis; communication disorder; complication; cultural factor; dept.cmd; female; genetics; human; infant; interpersonal communication; language; male; middle aged; phenotype; preschool child; psychological aspect; psychology; syndrome; young adult

Bivariate genetic analyses of stuttering and nonfluency in a large sample of 5-Year-Old twins - Beijsterveldt, Catharina Eugenie Maria Van; Felsenfeld, Susan; Boomsma, Dorret I (Journal of Speech Language and Hearing Research, 2010)
Purpose: Behavioral genetic studies of speech fluency have focused on participants who present with clinical stuttering. Knowledge about genetic influences on the development and regulation of normal speech fluency is limited. The primary aims of this study were to identify the heritability of stuttering and high nonfluency and to assess the relative contribution of genetic and environmental factors to the correlation between these 2 fluency phenotypes. Method: Information on 6 specific speech fluency behaviors was obtained by maternal report for over 10,500 5-year-old Dutch twin pairs. Results: Genetic analyses revealed that both fluency phenotypes were moderately heritable, with heritability estimates of 42% and 45% for probable stuttering and high nonfluency, respectively. Shared environmental factors were also significant, explaining 44% of the individual differences in probable stuttering and 32% in nonfluency. For both phenotypes, the magnitude of the genetic and environmental influences did not differ between boys and girls. The overlap between the 2 traits was substantial (tetrachoric correlation was .72). A bivariate genetic analysis showed that this overlap was due to both overlapping genetic and environmental influences. Conclusions: These findings provide a foundation to justify further studies in normal fluency control, a scientific area that has received little cross-disciplinary attention.
Keywords: Child Language; Child, Preschool; Cohort Studies; Environment; Female; Heritability; Humans; Male; Models, Genetic; Multivariate Analysis; Netherlands; Nonfluency; Phenotype; Probability; Questionnaires; Sex Factors; Speech Disorders; Stuttering; Twins; Twins, Dizygotic; Twins, Monozygotic; article; biological model; cohort analysis; dept.cmd; dizygotic twins; environment; female; genetics; human; language development; male; monozygotic twins; multivariate analysis; phenotype; preschool child; probability; questionnaire; sex difference; speech disorder; stuttering; twins

Impact and implications of word-finding difficulties in adolescents on listening comprehension assessment - Newman, Diana B (Communication Disorders Quarterly, 2010)
This investigation examined the listening comprehension (LC) performance of two groups of adolescent struggling readers, one group with word-finding difficulties (WFD) and one with no word-finding difficulties (NWFD). Of interest was whether the expressive language difficulties of the WFD group would interfere with their success on a LC assessment that requires oral responses to complete. Findings indicated that whereas the performance of the WFD group was comparable with the NWFD group when LC was measured using a multiple-choice response format, their performance was significantly poorer when LC was measured using an open-ended verbal response format, suggesting that learners' WFD could interfere with their success on such assessments. Practical implications of these findings for the assessment of LC as part of adolescents' reading evaluations are discussed. © 2010 Hammill Institute on Disabilities.
Keywords: adolescent; article; child; comprehension; controlled study; dept.cmd; human; language disability; listening comprehension; mental performance; multiple choice test; priority journal; reading; reading assessments; school child; task performance; word finding difficulty; word recognition; word-finding

Delayed Language Development in Preschool Children - Weiss, Deborah; Paul, Rhea (The Handbook of Language and Speech Disorders, 2010)
Keywords: "delayed language development" (DLD); "specific language impairment" (SLI); Delayed language development in preschool children; Developing language stage; Intervention for children with DLD; Language development and departure from typical acquisition in preschool children; Linguistic Characteristics of Children with DLD; Speech disorders; Language disorders; Communicative disorders; Speech-language pathologist (SLP)-primarily because their speech contains frequent articulation errors; Targets for vocabulary training for preschoolers with DLD; delayed language development in preschool children; dept.cmd; developing language stage; faculty_collection; intervention for children with DLD; language development and departure from typical acquisition in preschool children; speech-language pathologist (SLP) - primarily because their speech contains frequent articulation errors; targets for vocabulary training for preschoolers with DLD; “delayed language development” (DLD); “specific language impairment” (SLI)

Babysitter training guide for families with individuals with ASD - Bean, K; Neers, K; Cook, Barbara; Eren, R (Encyclopedia of Autism Spectrum Disorders, 2020)
The Second Edition of this major reference work expands its coverage and continues to break new ground as an electronic resource for students, educators, researchers, and professionals. Comprehensive in breath and textbook in depth, the Second Edition of the Encyclopedia of Autism Spectrum Disorders serves as a reference repository of knowledge in the field as well as a regularly updated conduit of new knowledge long before such information trickles down from research to standard textbooks. The Second Edition of the Encyclopedia digests and presents new and updated information for readers who need to stay current with the latest research and clinical practices, including advances in neurobiology and genetics, diagnostic instruments and assessment tests, pharmaceutical treatments, and behavioral, speech and language, and other rehabilitative therapies. The Second Edition of the Encyclopedia covers topics across the following major conceptual areas of ASD and PDDs, including: Research trends and findings Behavior/speech Communication TreatmentsEducation Taking advantage of the techniques offered by the electronic medium, the Second Edition of the Encyclopedia of Autism Spectrum Disorders offers an extensive cross-referencing system facilitating search and retrieval of information. This unique, comprehensive Second Edition of the Encyclopedia of Autism Spectrum Disorders is an essential reference for advanced undergraduate and graduate students as well as researchers, professors, clinicians, and other practitioners across such related disciplines as developmental psychology, child and adolescent psychiatry, social work, child and school psychology, behavioral therapy, and sociology of education.
Keywords: dept.cmd

Diagnostic and treatment outcomes for an adolescent with left functional hemispherectomy - McCullagh, Jennifer; Dilaj, K (Adult Audiology Casebook, 2019)
Keywords: dept.cmd; faculty_collection

Dichotic listening training following neurological injury in adults: a pilot study - Purdy, Mary; McCullagh, Jennifer (Hearing, Balance and Communication, 2019)
Purpose: Injury to the dominant left brain hemisphere can lead to specific language deficits such as aphasia, or to the cognitive processes that support language such as attention and working memory. Language is heavily supported through the auditory modality, which is a key area of deficit in acquired language disorders, and recovery of auditory processing is a prerequisite to recovery of other language modalities. A specific auditory processing deficit that has been identified following neurologic injury is dichotic listening. Some researchers have suggested that dichotic listening can be strengthened through the use of a dichotic listening training paradigm, although the impact of this training for adults with neurological injury is unknown. The purpose of this study was to determine whether dichotic listening training improved dichotic listening performance as well as auditory comprehension in individuals with neurological injuries.Method: Five individuals with a history of acquired language deficits who met specific inclusion and exclusion criteria participated in the dichotic listening training for four to six weeks. Dichotic listening and language comprehension skills were evaluated pre- and post-training.Results: Results indicated all participants progressed through a range of dichotic listening tasks during training, and four of the five individuals improved on at least one of the dichotic listening tests post-treatment. All of the participants demonstrated some improvement in auditory processing/comprehension of complex commands.Conclusions: Dichotic listening training has the potential to positively influence dichotic listening and auditory comprehension skills in adults with neurological injury.
Keywords: Article; Dichotic listening; adult; auditory processing; auditory processing disorder; auditory rehabilitation; brain injury; cerebrovascular accident; clinical article; comprehension; dept.cmd; dichotic listening; distortion product otoacoustic emission; hearing impairment; human; language ability; language disability; male; neurologic; peer-reviewed; pilot study; priority journal; pure tone audiometry; treatment; tympanometry

College Access, Success and Equity for Students on the Autism Spectrum. - Accardo, Amy L; Bean, Kimberly; Cook, Barbara; Gillies, Ann; Edgington, Rebecca; Kuder, S Jay; Bomgardner, Estyr M (Journal of autism and developmental disorders, 2019)
College may be considered a gateway to success, yet access to college is limited for young adults with autism. Given the research recommendations to elicit student experiences and to communicate among universities to improve college access, success, and equity, the present study examined the questions: What factors are perceived as pathways to success or barriers to success by college students on the autism spectrum? What university provided accommodations and/or support services do they prefer? Participants from four universities completed surveys and semi-structured interviews. Findings from the multi-university study suggest the need to provide transition planning and systematic non-academic social and emotional supports from the start of the college experience as well as specific training for faculty, staff, and peers.
Keywords: *Academic Success; *Autism Spectrum Disorder/rh [Rehabilitation]; *Mainstreaming, Education/sn [Statistics & Numerical Data]; *Universities/sn [Statistics & Numerical Data]; Academic Success; Accommodations; Adolescent; Article; Autism Spectrum Disorder; Autism Spectrum Disorder/px [Psychology]; Autism spectrum disorder; College; Female; Humans; Mainstreaming, Education; Male; Mental health; Students; Students/px [Psychology]; Students/sn [Statistics & Numerical Data]; Universities; University; Young Adult; academic success; adolescent; adult; autism; college; college student; dept.cmd; dept.sed; disability; executive function; female; financial management; follow up; health equity; human; longitudinal study; male; mental health care; motivation; peer-reviewed; priority journal; psychology; self concept; semi structured interview; social network; social support; student; student attitude; university; young adult

Adult swallow screening and clinical swallow evaluations - Suiter, Debra; Warner, Heather L. (Assessing and treating dysphagia: A lifespan perspective, 2019)
The definitive educational guide on the diagnosis and management of dysphagia across the full age continuumDysphagia presentation and treatment differs at various stages of life. Assessing and Treating Dysphagia: A Lifespan Perspective reflects significant knowledge and pearls from esteemed adult and pediatric swallowing disorders experts. Debra Suiter and Memorie Gosa have compiled a book of unique depth and breadth with contributions from communication science experts including speech-language pathologists and physicians. The textbook provides comprehensive coverage of swallowing disorders from birth to old age, including clinical, professional, and cultural ethical considerations.Key HighlightsAnatomy and physiology of swallowing, and compensatory, postural, and rehabilitation strategiesAdult and pediatric specific chapters on swallow screenings, clinical evaluations, and technologies such as videofluroscopic, fiberoptic endoscopic, and high-resolution manometryPediatric-specific dysphagia related to premature birth, craniofacial syndromes, congenital heart disease, and cerebral palsyAdult-specific dysphagia related to neurodegenerative disease, stroke, traumatic brain injury, head and neck cancer, esophageal disease, pulmonary disease, and end of lifeThis is the only textbook on the market featuring complete coverage of the diagnosis and management of dysphasia across the lifespan. With content following Master's-level course curriculum, this is essential reading for graduate students as well as practicing clinicians in the fields of otolaryngology and speech language pathology.This book includes complimentary access to a digital copy on https://medone.thieme.com.
Keywords: dept.cmd

Reading comprehension treatment in aphasia: A systematic review - Purdy, Mary; Coppens, Patrick; Madden, Elizabeth Brookshire; Mozeiko, Jennifer; Patterson, Janet; Wallace, Sarah E.; Freed, Donald (Aphasiology, 2019)
Background: Reading difficulties often present as a consequence of aphasia. The specific nature of reading deficits varies widely in manifestation, and the cause of these deficits may be the result of a phonological, lexical semantic, or cognitive impairment. Several treatments have been developed to address a range of impairments underlying reading difficulty.Aims: The purpose of this review is to describe the current research on reading comprehension treatments for persons with aphasia, assess the quality of the research, and summarize treatment outcomes.Methods & Procedures: A systematic review of the literature was conducted based on a set of a priori questions, inclusion/exclusion criteria, and pre-determined search parameters. Results were summarized according to treatment type, methodologic rigor, and outcomes.Outcomes & Results: Fifteen studies meeting criteria were identified. A variety of reading comprehension treatments was implemented including: oral reading, strategy-based, cognitive treatment, and hierarchical reading treatments. Quality ratings were highly variable, ranging from 3 to 9 (on a 12-point scale). Overall, 14 of the 18 individuals for whom individual data were provided demonstrated some degree of improvement (oral reading 4/5 participants, strategy based 4/6, and cognitive treatment 6/7). Gains were also evident for hierarchical reading treatment administered to participant groups via computer; however, the degree to which improvement reached statistical significance varied among studies.Conclusions: Reading comprehension treatments have the potential to improve reading comprehension ability in persons with aphasia; however, outcomes were variable within and among treatment methods. We suggest focusing future research on factors such as participant candidacy and treatment intensity using increased methodological rigor.
Keywords: Aphasia; Mini Mental State Examination; Review; agraphia; aphasia; certification; cognition; cognitive defect; communication skill; comprehension; deep learning; dementia; dept.cmd; dyslexia; episodic memory; human; interrater reliability; language test; motivation; peer-reviewed; phonetics; psychometry; quality of life; randomized controlled trial (topic); reading; reading comprehension; scientific literature; social hierarchy; stamen; systematic review; treatment; treatment outcome; word recognition; working memory

Relationship Between Laryngeal Sensation, Length of Intubation, and Aspiration in Patients with Acute Respiratory Failure. - Borders, James C; Fink, Daniel; Levitt, Joseph E; McKeehan, Jeffrey; McNally, Edel; Rubio, Alix; Scheel, Rebecca; Siner, Jonathan M; Taborda, Stephanie Gomez; Vojnik, Rosemary; Warner, Heather; White, S David; et al. (Dysphagia, 2019)
Dysphagia is common in hospitalized patients post-extubation and associated with poor outcomes. Laryngeal sensation is critical for airway protection and safe swallowing. However, current understanding of the relationship between laryngeal sensation and aspiration in post-extubation populations is limited. Acute respiratory failure patients requiring intensive care unit admission and mechanical ventilation received a Flexible Endoscopic Evaluation of Swallowing (FEES) within 72 h of extubation. Univariate and multivariable analyses were performed to examine the relationship between laryngeal sensation, length of intubation, and aspiration. Secondary outcomes included pharyngolaryngeal secretions, pneumonia, and diet recommendations. One-hundred and three patients met inclusion criteria. Fifty-one patients demonstrated an absent laryngeal adductor reflex (LAR). Altered laryngeal sensation correlated with the presence of secretions (p = 0.004). There was a significant interaction between the LAR, aspiration, and duration of mechanical ventilation. Altered laryngeal sensation was significantly associated with aspiration on FEES only in patients with a shorter length of intubation (p = 0.008). Patients with altered laryngeal sensation were prescribed significantly more restricted liquid (p = 0.03) and solid (p = 0.001) diets. No relationship was found between laryngeal sensation and pneumonia. There is a high prevalence of laryngeal sensory deficits in mechanically ventilated patients post-extubation. Altered laryngeal sensation was associated with secretions, aspiration, and modified diet recommendations especially in those patients with a shorter length of mechanical ventilation. These results demonstrate that laryngeal sensory abnormalities impact the development of post-extubation dysphagia.
Keywords: *Intubation, Intratracheal/ae [Adverse Effects]; *Laryngeal Diseases/et [Etiology]; *Pneumonia, Aspiration/et [Etiology]; *Sensation Disorders/et [Etiology]; Acute Disease; Acute respiratory failure; Article; Critical illness; Deglutition; Deglutition disorders; FEES; Female; Flexible Endoscopic Evaluation of Swallowing; Humans; Intubation, Intratracheal; Laryngeal Diseases; Laryngeal Diseases/pp [Physiopathology]; Laryngeal sensation; Larynx; Larynx/pp [Physiopathology]; Male; Middle Aged; Pneumonia, Aspiration; Prospective Studies; Respiratory Insufficiency; Sensation Disorders; Sensation Disorders/pp [Physiopathology]; Time Factors; absent laryngeal adductor reflex; acute disease; acute respiratory failure; adult; adverse event; artificial ventilation; aspiration; aspiration pneumonia; bodily secretions; clinical outcome; clinical trial; cohort analysis; controlled study; critical illness; dept.cmd; dietary intake; disease association; dysphagia; endotracheal intubation; extubation; female; hospital admission; human; intensive care; larynx; larynx disorder; lung aspiration; major clinical study; male; middle aged; multicenter study; nutritional requirement; outcome assessment; pathophysiology; peer-reviewed; pharyngolaryngeal secretions; pneumonia; prescription; prevalence; priority journal; prospective study; reflex disorder; respiratory failure; sensory dysfunction; time factor

Evaluation of Swallow Function Post-Extubation: Is It Necessary to Wait 24 Hours?. - Leder, Steven B; Warner, Heather L; Suiter, Debra M; Young, Nwanmegha O; Bhattacharya, Bishwajit; Siner, Jonathan M; Davis, Kimberly A; Maerz, Linda L; Rosenbaum, Stanley H; Marshall, Peter S; Pisani, Margaret A; Siegel, Mark D; et al. (The Annals of otology, rhinology, and laryngology, 2019)
BACKGROUND: Post-extubation dysphagia is associated with an increased incidence of nosocomial pneumonias, longer hospitalizations, and higher re-intubation rates. The purpose of this study was to determine if it is necessary to delay swallow evaluation for 24 hours post-extubation., METHODS: A prospective investigation of swallowing was conducted at 1, 4, and 24 hours post-extubation to determine if it is necessary to delay swallow evaluation following intubation. Participants were 202 adults from 5 different intensive care units (ICU)., RESULTS: A total of 166 of 202 (82.2%) passed the Yale Swallow Protocol at 1 hour post-extubation, with an additional 11 (177/202; 87.6%) at 4 hours, and 8 more (185/202; 91.6%) at 24 hours. Only intubation duration >=4 days was significantly associated with nonfunctional swallowing., CONCLUSIONS: We found it is not necessary to delay assessment of swallowing in individuals who are post-extubation. Specifically, the majority of patients in our study (82.2%) passed a swallow screening at 1 hour post-extubation.
Keywords: *Airway Extubation; *Deglutition Disorders/di [Diagnosis]; *Speech-Language Pathology/mt [Methods]; Adult; Aged; Aged, 80 and over; Airway Extubation; Article; Deglutition Disorders; Female; Humans; Intensive Care Units; Male; Middle Aged; Prospective Studies; Respiration, Artificial; Respiratory Insufficiency; Respiratory Insufficiency/th [Therapy]; Speech-Language Pathology; Time Factors; Young Adult; adult; aged; artificial ventilation; clinical assessment; clinical evaluation; clinical practice; controlled study; deglutition; deglutition disorders; dept.cmd; dysphagia; endotracheal intubation; extubation; female; hospitalization; human; intensive care unit; major clinical study; male; mental health; middle aged; oral alimentation; peer-reviewed; priority journal; procedures; prospective study; respiratory failure; speech disorder; speech language pathologist; swallowing; swallowing assessment; therapy delay; time factor; treatment duration; very elderly; young adult

Auditory p300 in noise in younger and older adults - McCullagh, Jennifer; Shinn, Jennifer B. (Journal of the American Academy of Audiology, 2018)
Background: Older adults often report difficulty hearing in background noise which is not completely attributable to peripheral hearing loss. Although age-related declines in cognition and hearing in back-ground noise occur, the underlying age-related changes in processing of auditory stimuli in background noise has yet to be fully understood. The auditory P300 has the potential to elucidate the effects of age on auditory and cognitive processing of stimuli in background noise, but additional research is warranted. Purpose: The purpose of this study was to investigate age-related differences in cognitive processing of auditory stimuli by evoking the auditory P300 at multiple signal-to-noise ratios (SNRs). Research Design: A two-group, repeated measures study design was used. Study Sample: A convenience sample of 35 participants, 15 older adults (mean age of 66.4 yr) and 20 younger adults (mean age of 21.1 yr), participated in the study. All participants had negative otologic and neurological histories. Data Collection and Analysis: The auditory P300 was evoked using an oddball paradigm with 500 (frequent) and 1000 Hz (target) tonal stimuli in quiet and in the presence of background noise at +20, +10, and 0 SNRs. P300 amplitudes and latencies were measured in each condition for every participant. Repeated measures analyses of variance were conducted for the amplitude and latency measures of the P300 for each group. Results: Results from this study demonstrated P300 latencies were significantly longer in older adults in noise at the most challenging condition (0 SNR) compared with the quiet condition and between the +10 SNR and 0 SNR conditions. Although older adults had significantly longer P300 latencies compared with younger adults, no significant group by listening condition interaction existed. No significant P300 amplitude differences were found for group, noise, or group x listening condition interactions. Conclusions: Results provide evidence that auditory cortical processing, regardless of age, is poorer at more difficult SNRs. However, results also demonstrate that older adults perform significantly poorer than younger adults. This supports the notion that some degree of age-related decline in synchronous firing and rate of transmission of the auditory cortical neurons contributing to the auditory P300 exists. Studies are needed to further understand the impact of noise on auditory cortical processing across populations.
Keywords: Acoustic Stimulation; Aged; Aging; Auditory Cortex; Auditory Perception; Auditory Threshold; Cognition; Conference Paper; Evoked Potentials, Auditory; Female; Hearing in noise; Humans; Male; P300; Reference Values; Young Adult; adult; aged; auditory cortex; auditory evoked potential; auditory stimulation; auditory threshold; brain cell; clinical article; cognition; comparative study; convenience sample; dept.cmd; female; hearing; hearing acuity; hearing impairment; human; latent period; male; medical history; mental deterioration; noise; otoscopy; outcome assessment; peer-reviewed; physiology; priority journal; procedures; pure tone audiometry; reference value; signal noise ratio; white noise; working memory; young adult

Communication and cognition - LaPointe, Leonard L.; Stierwalt, Julie; Purdy, Mary H. (Aphasia and related neurogenic language disorders, 2018)
Rapid advances in neural imaging, particularly in regard to neural plasticity and brain changes, have resulted in an evolving neurorehabilitation paradigm for aphasia and related language disorders. Aphasia and Related Neurogenic Language Disorders has been adopted worldwide as a text for aphasia courses. This new 5th edition by Leonard LaPointe and Julie Stierwalt encompasses state-of-the-art concepts and approaches from an impressive cadre of experts who work in research labs, classrooms, clinics, and hospitals-including the world-renowned Mayo Clinic.As in previous editions, this book embraces a humanistic approach to treatment, addressing multicultural and multilinguistic considerations and social model interventions. The text encompasses a full continuum of cognitive-language disorder management-from everyday practicalities, assessment, and treatment to disorder-specific cases with evidence-based data. Additions to the 5th edition include chapters on pragmatics and discourse, telepractice, digital and electronic advances, funding and reimbursement, and comprehension, syntax, and linguistic based disorders.Key Features:A new chapter on neuroanatomical basics features exquisite illustrationsAn in-depth look at neurogenic communication disorders from Mayo Clinic provides firsthand insights on treating patients in an acute care hospital settingDiscussion and test questions, case studies, and clinical pearls offer invaluable didactic guidanceA chapter on expanded traumatic brain injury covers blast injuries and multisystem injuriesThis is the most comprehensive yet concise resource on aphasia and related disorders available today. New legions of speech language pathology students, residents, course directors, and practitioners will discover a remarkable guide on the treatment of communication disorders.
Keywords: dept.cmd

Social Pragmatic Communication and Literacy in African American English Speakers - Hyter, Yvette D.; DeJarnette, Glenda; Rivers, Kenyatta O. (Perspectives of the ASHA Special Interest Groups, 2018)
Keywords: dept.cmd; peer-reviewed

Comparing simultaneous clinical swallow evaluations and fiberoptic endoscopic evaluations of swallowing: Changing practice patterns - Leder, Steven B.; Warner, Heather L. (Perspectives of the ASHA Special Interest Groups, 2018)
Keywords: dept.cmd; peer-reviewed

Effectiveness of a preexternship hospital orientation program for graduate students in speech-language pathology - Warner, Heather; Karlberg, Amy; Purdy, Mary (Perspectives of the ASHA Special Interest Groups, 2018)
Keywords: dept.cmd; peer-reviewed

Interpersonal supports - Cook, Barbara (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

Relationship enhancement methods - Cook, Barbara (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

Peer mentors for students with ASD on college campuses - Cook, Barbara; Weiss, Deborah (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

A facilitated natural mentoring program: Young adults with autism learn to negotiate college life in a class with university students - Cook, Barbara; Weiss, Deborah; Hodge, Virginia (The ASHA Leader, 2017)
Young adults with autism learn to negotiate college life in a class with university students. © 2017 American Speech-Language-Hearing Association.
Keywords: dept.cmd

Electrophysiological Indices of Audiovisual Speech Perception in the Broader Autism Phenotype. - Irwin, Julia; Avery, Trey; Turcios, Jacqueline; Brancazio, Lawrence; Cook, Barbara; Landi, Nicole (Brain sciences, 2017)
When a speaker talks, the consequences of this can both be heard (audio) and seen (visual). A novel visual phonemic restoration task was used to assess behavioral discrimination and neural signatures (event-related potentials, or ERP) of audiovisual processing in typically developing children with a range of social and communicative skills assessed using the social responsiveness scale, a measure of traits associated with autism. An auditory oddball design presented two types of stimuli to the listener, a clear exemplar of an auditory consonant-vowel syllable /ba/ (the more frequently occurring standard stimulus), and a syllable in which the auditory cues for the consonant were substantially weakened, creating a stimulus which is more like /a/ (the infrequently presented deviant stimulus). All speech tokens were paired with a face producing /ba/ or a face with a pixelated mouth containing motion but no visual speech. In this paradigm, the visual /ba/ should cause the auditory /a/ to be perceived as /ba/, creating an attenuated oddball response; in contrast, a pixelated video (without articulatory information) should not have this effect. Behaviorally, participants showed visual phonemic restoration (reduced accuracy in detecting deviant /a/) in the presence of a speaking face. In addition, ERPs were observed in both an early time window (N100) and a later time window (P300) that were sensitive to speech context (/ba/ or /a/) and modulated by face context (speaking face with visible articulation or with pixelated mouth). Specifically, the oddball responses for the N100 and P300 were attenuated in the presence of a face producing /ba/ relative to a pixelated face, representing a possible neural correlate of the phonemic restoration effect. Notably, those individuals with more traits associated with autism (yet still in the non-clinical range) had smaller P300 responses overall, regardless of face context, suggesting generally reduced phonemic discrimination.
Keywords: Article; Audiovisual speech perception; Broader autism phenotype; Development; ERP; audiovisual aid; audiovisual equipment; audiovisual speech perception; autism; behavior; broader autism phenotype; child; clinical article; dept.cmd; dept.hls; dept.psy; development; electrophysiology; female; human; male; participant observation; phenotype; social adaptation; social competence; speech perception; stimulus; vision test

Risk of reading difficulty among students with a history of speech or language impairment: Implications for Student Support Teams - Zipoli, Richard P.; Merritt, Donna D. (Preventing School Failure: Alternative Education for Children and Youth, 2017)
Many students with a history of speech or language impairment have an elevated risk of reading difficulty. Specific subgroups of these students remain at risk of reading problems even after clinical manifestations of a speech or language disorder have diminished. These students may require reading intervention within a general education system of supports and services. The first part of this article describes three speech-language disorders that place elementary students at risk of reading problems: functional speech disorders, childhood apraxia of speech, and specific language impairment. Emphasis is given to research findings on the reading outcomes of students with these disorders. The second part of the article provides recommendations within an RTI framework that will assist Student Support Teams in identifying, monitoring, and supporting these students. © 2017 Taylor & Francis Group, LLC.
Keywords: Assessment; Language impairment; RTI; Reading disability; Speech sound disorders; dept.cmd; peer-reviewed

Unraveling difficult sentences: strategies to support reading comprehension - Zipoli, Jr., Richard P. (Intervention In School And Clinic, 2017)
The ability to understand sentences contributes to students' reading comprehension. However, many reading programs tend to underemphasize explicit instruction aimed at enhancing students' knowledge of sentence structures. Children with language impairments, students with learning disabilities, and English language learners may particularly benefit from instruction that targets potentially challenging sentence structures. This article is designed to help educators and clinicians more effectively identify and teach several sentence structures that can compromise elementary and middle school students' understanding of written text. Four types of sentence structures that may be difficult to process are introduced and systematically explored: (a) sentences with passive verb constructions, (b) adverbial clauses with temporal and causal conjunctions, (c) center-embedded relative clauses, and (d) sentences with three or more clauses. Information is presented on syntactic structures, sources of confusion, developmental considerations, assessment caveats, and instructional strategies.
Keywords: dept.cmd; peer-reviewed; reading comprehension; reading instruction; sentence comprehension; syntax

The effects of auditory training on dichotic listening: A neurological case study - McCullagh, Jennifer; Palmer, Shannon B. (Hearing, Balance and Communication, 2017)
Background: Individuals with neurological impairment have been shown to have deficits in auditory processing abilities. One auditory processing ability shown to be affected is dichotic listening. To date, limited evidence exists demonstrating the effectiveness of dichotic listening intervention on dichotic listening in individuals with neurological impairment. The purpose of this study was to determine the effects of the dichotic listening training on dichotic listening abilities over multiple training periods in an individual with a long-standing and stable neurological history. Method: This study used a case study design. Over the course of 3 years, an individual with dichotic listening deficits following a left cerebral vascular accident underwent multiple auditory training periods using a dichotic listening training paradigm. Initial assessments indicated a bilateral deficit on the Dichotic Digits test with the right ear performing more poorly than the left ear and a right ear deficit on the Dichotic Rhyme test. Training sessions took place 2–3 times per week for a period of 4–11 weeks in the years 2012, 2013 and 2014. Pre- and post-training assessments of dichotic listening and hearing in noise ability were completed for each training period. Results: Results indicated improvements in the trained (right) ear on the Dichotic Digits test following each of the three training periods. Results also indicated stable performance in the right ear on the Dichotic Rhyme test and variable performance on the Words-in-Noise (WIN) test following each training session. Performance on the Dichotic Digits test decreased slightly between training periods; however, overall performance showed improvement over time. Conclusion: These results suggest improved binaural integration abilities as measured by the Dichotic Digits test following dichotic listening training in an individual with neurological impairment. However, the effects of the training did not transfer to tasks of binaural fusion (Dichotic Rhyme test) or hearing in noise (WIN test) tasks. © 2016 International Association of Physicians in Audiology.
Keywords: Article; Auditory training; adult; aphasia; auditory evoked potential; auditory processing disorder; carotid artery obstruction; case report; cerebrovascular accident; dept.cmd; dichotic listening; distortion product otoacoustic emission; follow up; general condition improvement; human; left hemisphere; male; neurological impairment; noise; nuclear magnetic resonance imaging; patient referral; peer-reviewed; priority journal; pure tone audiometry; speech and language rehabilitation; speech audiometry; speech language pathologist; training; tympanometry